Biochemical oxidation-mediated simultaneous removal of manganese and sulfamethazine in solar-activated algal-MnOBacteria symbiotic membrane bioreactor - Xing Du; Zhitao Zhang; Zhihong Wang; Wei Song; Dachao Lin; Fangshu Qu (Water Research, 2027)

Background-associated skin color change in seahorses: genetic bases, evolutionary adaptations and implications for ornamental aquaculture - Yingyi Zhang; Haiyan Yu; Chao Zhang; Qiang Lin; Meng Qu (Reviews in Fish Biology and Fisheries, 2026)

Drainage alters bacterial co-occurrence networks and net nitrogen mineralization rate in peatlands under different forest management regimes - Ning Li; Yunuo Hu; Zhao-lei Qu; Heidi Aaltonen; Marjo Palviainen; Annamari Laurén; Frank Berninger; Xudan Zhu; Anne Ojala; Lin Huang; Hui Sun; Jukka Pumpanen (Agriculture, Ecosystems & Environment, 2026)

Farrerol improves the maturation quality of porcine oocytes derived from small follicles associated with RAD51-related DNA repair responses - Lin Qi; Yingting Pan; Chaoqun Qu; Shuangyan Mo; Cuiting Peng; Hao Xie; Yulan Zhao; Yijie Tang; Wei Shen; Zhilong Chen; Zhonglin Tang (Theriogenology, 2026)

Janus membrane with sacrificial carboxymethyl chitosan layer for in situ silica scaling mitigation in membrane distillation - Zhongsen Yan; Zeqi Yan; Sufen Lin; Haiqing Chang; Kaiqin Xu; Gongduan Fan; Fangshu Qu (Desalination, 2026)

Water Management Controls Thiacloprid Degradation in Soil via Iron Redox Cycling with Biochar-Supported Zero-Valent Iron - Lin Pan; Shuai Qu; Longfei Liu; Wan Yang; Muhammad Mahroz Hussain; Shengsen Wang (Water, Air, & Soil Pollution, 2026)

Adsorption Performance and Mechanism of Ni(II) by EDTA-Catalyzed Mg/Al Hydroxide-Modified Biochar - Weiping Sima; Jiang Qu; Qibin Xu; Hengjun Tang; Lin Wang (Water, Air, & Soil Pollution, 2026)

Experimental study on wave attenuation through living shorelines of submerged breakwater and marsh vegetation - Qianru Lin; Xiaodong Liu; Huajun Li; Bingchen Liang; Zhipeng Qu; Wenxiao Zhuge (Ocean Engineering, 2026)

3D Co, N co-doped carbon dots/TiO2 heterostructures: Unlocking radical-nonradical dual-pathway synergy in efficient PMS photo-activation - Pengze Wang; Jing Liang; Zhijun Li; Yang Qu; Pengkai Shen; Ziyu Chen; Junkang Lin; Rui Yan; Jing Wu; Liqiang Jing (Journal of Environmental Chemical Engineering, 2026)

A biomass asymmetric fabric evaporator based on waste corn stalks for efficient solar evaporation and cogeneration - Mengnan Qu; Xinyi Tian; Jiehui Li; Yuanyuan Wang; Yuhang Gao; Ying Zhang; Zongrui Huang; Lin Liu; Chao Wang; Jinmei He (Journal of Environmental Chemical Engineering, 2026)

pH-dependent fouling mechanisms of polyamide Janus membrane during membrane distillation treatment of landfill leachate - Binbin Li; Zhongsen Yan; Yuandong Lin; Haiqing Chang; Yuting Lin; Huiyi Cai; Fangshu Qu (Journal of Environmental Chemical Engineering, 2026)

Photoexcited directional charge transfer channels on iron-doped bismuth oxybromide for efficient peroxymonosulfate activation in water treatment - Kai Teng; Yi Tao; Mengwei Wu; Chang Liu; YeFei Su; Jiangjun Lin; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2026)

Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

Maize attainable yields across China reveal unrealized potential for sustainable food security - Jingjing Wang; Zhijuan Liu; Zhenkang Yang; E Li; Jiangjiang Xia; Jingjin Gong; Huihui Qu; Tao Li; Xiaomao Lin; Xiaoguang Yang (Field Crops Research, 2026)

A memory-constrained multiscale pore network modeling framework for gas permeability prediction in compacted bentonite - Yongxiao Qu; Huaxiang Yan; Bo Li; LiGe Wang; Andrey P Jivkov; Weiguang Wang; Lin Ma; Mohsen Masihi; Qingrong Xiong (Computers and Geotechnics, 2026)

Deep-eutectic-solvent-assisted enzymatic valorization of Sepia pharaonis ink: flavoromics-guided bioactivity screening and microbiota–gut–brain axis-mediated attenuation of colitis-associated depression - Lin Liu; Jun Yang; Changfeng Qu; Jinlai Miao (Chemical Engineering Journal, 2026)

Sustainable mechanochromism and photochromism achieved by incorporating rhodamine into dialdehyde bacterial cellulose - Zheyu Shen; Qiuhao Yi; Bianjing Sun; Yalei Qiao; Xinyu Chen; Chenchen Qin; Lin Shi; Hongxia Qu; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Local lattice strain in layered double hydroxides enhances flexoelectric effect for hydraulically driven water disinfection - Muke Lin; Shulin Zuo; Weiqi Liu; Zhipeng Zhang; Ye Chen; Rumeng Zhang; Wei Qu; Zhuoyun Tang; Dehua Xia (Chemical Engineering Journal, 2026)

Chemical composition and bioactivities of the essential oils from three Curcuma species and one hybrid (C. attenuata × C. petiolata) against three stored-product insects - Hui Fan; Yuan Zhang; Jia-Zhu Wang; Xin-Xin Lu; Shu-Shan Du; Gong-Lin Qu (Journal of Plant Diseases and Protection, 2026)

Electronic configuration regulation and photocatalytic nitrogen fixation performance of the fourth-period d7/d8 metal catalysts - Xiaolu Xu; Jingyi Qu; Yangben Chen; Jiahui Lin; Yibo Zhang; Zhan Hu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Insight into the blocking effects of curcumin on histamine H1 receptor as a natural anti-food allergic compound - Wenjuan Jiang; Yan Qu; Ziye Zhang; Fatih Özogul; Zhenxing Li; Hong Lin (Food Bioscience, 2026)

Giant electrocaloric effect in bilayer BZT-BFO/Terpolymer nanocomposite films at a low electric field - Xiaodan Cao; Qing Qu; Dong Yang; Xin Zheng; Qinghang Zeng; Xiaoshi Qian; Zhong Lin Wang; Kailiang Ren (Chemical Engineering Journal, 2026)

Pathogen survival and antibiotic resistance gene persistence on hospital environmental surfaces: Short-lived disinfection efficacy may enables persistent contamination threat - Yunhan Jiang; Haiting Feng; Xiaoguang Guo; Bingni Zhang; Zhihao Lin; Jiyan Shi; Tingting Qu; Yunbo Chen; Chaofeng Shen (Building and Environment, 2026)

Impact of Cultivation on Soil Phosphorus Content along the Altitude Gradient in Alpine Forest of the Tibetan Plateau - Yuxuan Cui; Xu-Ri; Fengzi Li; Songbo Qu; Ribu Shama; Lin Zhang; Eryuan Liang (Journal of Soil Science and Plant Nutrition, 2026)

Information flow reveals three-tiered oceanic drivers of precipitation over the middle–lower Yangtze River Basin - Li-Ying Ning; Dan Wu; Ying Qu; Guo-Lin Feng; Yong-Ping Wu (Climate Dynamics, 2026)

Resveratrol alleviates heat stress of Hu sheep by modulating rumen biofilm-related microbial traits and enhancing serum antioxidant capacity - Qinghua Qiu; Chang Liu; Yuhang Ma; Lin Li; Kehui Ouyang; Mingren Qu (Animal Feed Science and Technology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Robust source tracing for solid waste via machine learning-enabled mineralogical fingerprinting - Le Lin; Changhai Ren; Shen Qu; Yang Xiao; Yin Li; Xueming Liu; Han Wang; Zhang Lin (Resources, Conservation and Recycling, 2026)

Electron-deficient boron-doped bimetallic (ZnFe) catalyst for high-efficiency photocatalytic nitrogen fixation - Xiaolu Xu; Jiahui Lin; Yangben Chen; Yibo Zhang; Zhan Hu; Jingyi Qu; Zhexiao Zhu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

The Use of Double-tube Multiplex TaqMan Real-time RT-PCR for the Simultaneous Detection of Foodborne Viruses in Shellfish - Peng Lin; Ling Chen; Qiang Wan; Zhihe Cai; Liang Xue; Qinghua Ye; Fufeng Jiang; Xiaoying Qu; Jiahui Huang; Huishu Huang; Yu Ding; Moutong Chen; et al. (Food Control, 2026)

Phosphate-induced polarization and defect engineering synergized with interfacial activation for dual-pathway H2O2 photosynthesis - Junnan Qu; Kaichi Chen; Jinhao Chen; Jiahao Lei; Zhicheng Zheng; Jingxuan Ren; Beinuo Zhang; Yukun Fang; Huiwen Lin; Yanmei Zheng; Xinli Guo (Chemical Engineering Journal, 2026)

Editorial Expression of Concern: Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2026)

Absolute configurations and anti-bacterial activity of two century-old maleidrides - Rongfang Qu; Chenyu Wu; Wenhao Mu; Yuxia Lou; Weibing Jiang; Minfeng Jin; Lin-Fu Liang; Fan Yang (Natural Product Research, 2026)

Tuning electron transfer and surface dual-sites for synergistic peroxymonosulfate activation toward efficient 2,4,6‑trichlorophenol degradation - Jingyi Wang; Yitong Liu; Wenhui Qiu; Lin Zhang; Kaige Li; Ran Wang; Bo Cao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

The mediation and interaction roles of hypertension on the pathway between occupational noise and cardiac arrhythmia: insights from a large cross-sectional occupational population of 229,686 workers - Zhiqiang Li; Wenjing Wu; Xinyue Li; Bing Xia; Shao Lin; Xiaowen Wang; Xudan Chen; Yanji Qu; Ziqiang Lin; Jinghua Li; Guanghui Dong; Yongshun Huang; et al. (Environmental Pollution, 2026)

Structural elucidation and distribution pattern of glucuronic acid in β-glucan from Hypsizygus marmoreus using glycosidase hydrolysis - Yunhe Qu; Ziyan Sun; Xiushi Jia; Yuanning Wang; Xing Yang; Yunmei Ma; Kevin H. Mayo; Lin Sun; Dongfang Shi; Yifa Zhou (Carbohydrate Polymers, 2026)

Environmental controls and nonlinear responses of the diatom-dinoflagellate ratio in Jiaozhou Bay - Yipeng Huang; Zhengguo Cui; Changhua Liu; Dongsheng Ding; Lin Zhu; Keming Qu; Yuqiu Wei; Jun Sun (Marine Pollution Bulletin, 2026)

Synthesis of composite seismic intensity measure based on Ridge Regression: Application to steel frame structures - Jiting Qu; Junwen Lin; Linsheng Huo (Soil Dynamics and Earthquake Engineering, 2026)

Enhanced human activities disturbed vegetation since 3500 years ago in southern China - Lin Zhao; Zijian Liu; Xiaoxu Qu; Zhongwei Shen; Zhiguo Rao; Xianyong Cao (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Cationic-functionalized tea stalk derived biochar for Cr(VI) remediation in environmental media: Synergistic reduction-adsorption mechanisms and environmental application - Jianhua Qu; Xuerui Liu; Chunying Lin; Jia Qi; Wei Peng; Enyang Mo; Haiyi Zhang; Tianqi Liu; Ying Zhang (Journal of Environmental Chemical Engineering, 2026)

A Janus-structured photothermal evaporator with black phosphorus for efficient and salt-resistant solar desalination - Mengnan Qu; Jin Zhang; Jiehui Li; Yuhang Gao; Ying Zhang; Mengge Cao; Zaiwen Yang; Lin Liu; Chao Wang; Jinmei He (Journal of Environmental Chemical Engineering, 2026)

Functional characterization of fungal laccases via siRNA silencing enables targeted biodegradation - Jiaqi Sun; Lianyan Yuan; Mengna Niu; Ping Xu; Jinsheng Lin; Cuixin Li; Lin Ma; Huiping Li; Qiang Wang; Shaoxuan Qu (Environmental Pollution, 2026)

Cathodic Fe2O3/Fe heterojunction engineering for highly selective electro-Fenton denitrification in agricultural tailwater - Ruijun Ren; Liye Liang; Jiangqi Qu; Qingjing Zhang; Yingzi Lin; Fei Qi; Chengxia Jia; Yanfei Wu (Chemical Engineering Journal, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Isolation and Cytotoxic Activities of Two New 2-Pyridone Alkaloids with Unique Structures from the Beibu Gulf Coral-Derived Acremonium sclerotigenum GXIMD 02501 - Yuning Qin; Xinjian Qu; Miaoping Lin; Hong Zhang; Huangxue Qin; Chenghai Gao; Yonghong Liu; Xuefeng Zhou; Xiaowei Luo (Journal of Ocean University of China, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

SlCNR promotes the lycopene accumulation and reduces abscisic acid content in postharvest tomato fruit - Shuai Zhang; Mingzhe Mang; Di Chen; Liqun Ma; Shiyuan Zhang; Tingting Hu; Lin Yu; Jiankang Cao; Daqi Fu; Benzhong Zhu; Hongliang Zhu; Guiqin Qu (Postharvest Biology and Technology, 2026)

Differential impacts of ocean acidification and alkalinization on shell microstructure and molecular responses in Mytilus edulis - Zhaohao Chen; Yubin Hu; Xiaoru Lin; Chenglong Lei; Yuanning Li; Yuan Wang; Chao Li; Zhishuai Qu; Jinzhe Du (Marine Environmental Research, 2026)

Film and hard capsule formation properties of the low-molecular-weight carrageenan - Huan Lin; Mengke Yao; Qing Zhang; Yingying He; Changfeng Qu; Jinlai Miao (Food Hydrocolloids, 2026)

Mechanical behavior and design of an eight-bolt extended stiffened end-plate connection with oversized holes: Experimental and numerical studies - Bin Jiang; Liping Duan; Siwei Lin; Jiming Liu; Ge Qu; Jincheng Zhao (Engineering Structures, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Downregulation of miR-194-5p impairs cardiomyocyte proliferation and differentiation through targeting Fign in congenital heart disease - Peishan Liang; Guangli Ren; Jie Zhu; Tingting Zhou; Yahong Chen; Jiangang Lin; Yiqiong Zhang; Xiangmeng Qu (Molecular and Cellular Biochemistry, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Holocene precipitation/humidity change trend in subtropical southern China: Contrary results, analyses and prospective - Xiaoxu Qu; Yunxia Li; Zhongwei Shen; Lin Zhao; Siyu Wu; Zhiguo Rao (Quaternary Science Reviews, 2026)

Biphasic toxicity of copper hydroxide nanopesticides to Microcystis aeruginosa: Mechanistic insights from physiological and transcriptomic responses - Yunfei He; Yue Yao; Qi Su; Qiulan Lin; Xuetong Qu; Jiafeng Ding; Hangjun Zhang (Journal of Water Process Engineering, 2026)

Synergistic co-composting of biogas residue and black soldier fly frass: Spectroscopic fingerprints of DOM evolution and nitrogen retention for sustainable food-waste recycling - Xiaolong Wu; Guangyu Cui; Yuxin Qu; Zehan Lin; Junjie Xu; Qiyong Xu (Journal of Environmental Chemical Engineering, 2026)

Crude oil biodegradation by synthetic microbial consortia: Performance and mechanisms under a top-down enrichment strategy - Wenya Wang; Qing Xiao; Ruiqi Lin; Hao Zhou; Yuanyuan Qu; Jingjing Zhan; Xuwang Zhang (Journal of Environmental Chemical Engineering, 2026)

The synergistic effects of ammonium and phosphorus on higher alcohol biosynthesis in Zygosaccharomyces mellis LGL-1 and its application for wampee/grape winemaking - Chunyun Qu; Zuyue Qi; Shuochun Lin; Jianjun Li; Yu Zeng; Yiyin Xu; Weidong Bai; Gongliang Liu (Food Microbiology, 2026)

Layered nitrogen application drives changes in nitrogen nutrition status of wheat by affecting key soil microbial clusters - Yang Zhou; Pengjia Wu; Yanjie Qu; Shengyan Pang; Haimeng Mu; Min Yang; Xiang Lin; Dong Wang (European Journal of Agronomy, 2026)

Optimization of fermentation conditions for recombinant McXyn0243 xylanase from Malbranchea cinnamomea and its application in producing xylooligosaccharides from sugarcane bagasse - Jinghao Ma; Lin Dai; Ruiwen Cheng; Fei Xiao; Yongbo Qu; Jianshan Fu; Jianhui Wen; Rana Abdul Basit; Dafeng Yin; Guangsen Fan (Biocatalysis and Agricultural Biotechnology, 2026)

Dietary bile acids supplementation enhances growth performance, nutrient digestion, hepatic function, rumen fermentation, and modulates quorum sensing in culled ewes - Chang Liu; Lin Li; Min Li; Kehui Ouyang; Mingren Qu; Qinghua Qiu (Animal Feed Science and Technology, 2026)

Integrating expert range maps and opportunistic occurrence records of marine fish species in range estimates - Zhixin Zhang; Ákos Bede‐Fazekas; Jorge García Molinos; Stefano Mammola; Jamie M. Kass; Junmei Qu; Julian Oeser; Songxi Yuan; Chongliang Zhang; Jiqi Gu; Liuyong Ding; Qiang Lin (Conservation Biology, 2026)
Species distribution models (SDMs) are commonly used to estimate species’ geographic distributions to inform biodiversity assessments and conservation planning. However, despite their growing popularity, range predictions of SDMs are affected by biases in opportunistic occurrence records and the lack of information on range limits. Integration of expert range maps in SDMs could help, but this strategy is still rarely used, especially for marine species. We built SDMs for 196 marine fish species with global distributions of Epinephelidae and Syngnathidae, 4 modeling algorithms, and opportunistic occurrence data. We then developed 2 types of SDM ensembles (i.e., combined predictions of multiple individual SDMs): with and without integration of expert range maps. We quantified the level of dissimilarity in range estimates between the 2 ensembles and explored the effects of taxonomic identity, geographic attributes, and conservation status on dissimilarity in model predictions. Although both types of ensembles had good predictive performance, ensembles informed by expert range maps avoided overpredictions of ranges past geographical barriers. Moreover, the dissimilarity between predictions of the 2 ensembles depended on multiple factors, including the number and extent of opportunistic occurrences, distance of occurrences to the expert range polygons, and fish family. Based on our findings, we recommend that researchers combine complementary information provided by expert range maps and opportunistic occurrences when predicting marine species distributions with SDMs.

How does recreation involvement in urban parks promote restorative effects? - Erkang Fu; Lin Li; Jiawen Zhou; Li Deng; Mingxuan Pu; Peilin Qu; Yijun Xu; Xi Li (Urban Forestry & Urban Greening, 2026)

Effects of blending ratios on flame temperature and alkali metal release mechanisms during co-firing of coal and refuse-derived fuel - Jian Zhang; Shu Zheng; Chenxuan Feng; Weiguang Cai; Hanglin Qu; Hongxu Liu; Yao Kong; Xiangyu Zhang; Lin Gao; Qiang Lu (Fuel, 2026)

Plasmid-mediated modulation of Listeria monocytogenes biofilm formation via TCS/PTS signaling: Implications for food contamination control - Jing Wang; Hui-Min David Wang; Yang Qu; Ting Lin; Changyan Zhou; Zijie Lin; Yangtai Liu; Zhuosi Li; Qingli Dong; Yujuan Suo (Food Research International, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Dietary 4-hydroxy-2,5-dimethyl-3(2 H)-furanone supplementation enhances serum antioxidant capacity and nutrient digestibility in Hu sheep by promoting biofilm formation - Qinghua Qiu; Chuanpei Fu; Lin Li; Kehui Ouyang; Mingren Qu (Animal Feed Science and Technology, 2026)

Ecological drivers of multidimensional temporal beta diversity of phytoplankton communities in a temperate lake over 20 years - Xiaoguang Zhang; Yueming Qu; Qinghua Cai; Lin Ye (Aquatic Ecology, 2026)

Acidification and deoxygenation matter in assessing redistribution of global cold‐water coral biodiversity induced by climate change - Shuaishuai Liu; Bingqing Xiao; Ákos Bede‐Fazekas; Stefano Mammola; Jorge García Molinos; Jamie M. Kass; Jorge Assis; Chen Lin; Junmei Qu; Hongwei Huang; Qiang Lin; Zhixin Zhang (Limnology and Oceanography, 2026)
The ocean is undergoing significant changes, including warming, acidification, and deoxygenation, which pose great challenges to marine biodiversity. However, most models projecting the impacts of climate change on marine species overlook predictor variables critically meaningful for species' ecologies such as pH and dissolved oxygen. The recent release of high‐resolution projections of different future climate‐change scenarios offers the opportunity to explore species redistribution under multiple threats beyond ocean warming. Accordingly, we conducted a global comparative analysis to study the impact of incorporating predictor variables describing pH and dissolved oxygen into marine species distribution models. We used models trained for 268 cold‐water coral species to project potential future distributions for different climate and dispersal scenarios over different time periods. We found that, irrespective of scenario or period, models using pH and dissolved oxygen projected 11.5–21.4% higher impacts of climate change than those without them. For instance, by the end of the century under a high emission scenario, models including pH and oxygen projected an average range contraction of 48.2% for cold‐water corals under a no‐dispersal scenario, compared with a 26.8% contraction projected by models excluding these two predictors. Given the substantial differences in the predicted distribution patterns and the biological importance of these variables, we highlight that researchers should consider more diverse sets of predictor variables when predicting future range shifts for marine biodiversity assessments under climate change.

A novel phage and its protective effects against Hafnia paralvei in Cyprinus carpio Koi - Lingting Pan; Chenxin Qu; Wencai Liu; Long Tan; Xiaoying Jing; Jinpeng Xu; Wei Lin; Dengfeng Li; Yigang Tong (Aquaculture, 2026)

Insights into co-occurrence characteristics and interplay of microbial communities and environmental pollutants on biofilm-colonized microplastics in mangrove ecosystems - Tao Yang; Xudong Ye; Xi Deng; Jun Mu; Min Liu; Jianhui Lin; Yuangao Qu; Yingxu Zeng (Water Research, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Diurnal double-pulse of nitrate dynamics in Mount Qomolangma glacial runoff - Dandan Yang; Lin Li; Tandong Yao; Baiqing Xu; Jing Gao; He Sun; Dongmei Qu (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The influence of environmental factors on anthocyanin biosynthesis in fruits - Zhang Xiangzhao; Zhao Lin; Xu Xu; Zhu Jialing; Qu Shenchun; Wang Sanhong (Plant Science, 2026)

Time-resolved fluorescence imaging of methylene blue reveals heterogeneous polarity in living cells - Andrey V. Belashov; Anna A. Zhikhoreva; Zhenlong Huang; Fangrui Lin; Irina V. Semenova; Oleg S. Vasyutinskii; Junle Qu (Journal of Photochemistry and Photobiology B: Biology, 2026)

Tailoring pH-switchable self-dispersible N-halamine microspheres as multifunctional additives for lyocell fibers - Jie Zhao; Lian-Yi Qu; Jiang-Long Liu; Lin Zhang; Zhi-Ming Jiang; Yun Liu; Ying-Jun Xu (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Unveiling the choroidal immune landscape revealed interferon-gamma and TNF-alpha as novel therapeutic targets in dry AMD - Lin Ye; Tujing Zhao; Huaping Tian; Runze Li; Zheng Li; Hongjing Li; Ruilin Liao; Junlan Chuan; Haojue Xu; Liang Zou; Chao Qu; Yi Shi; et al. (Science China Life Sciences, 2026)

Two novel TRAF homologs are implicated in the immunological response and interact with IRAK in the Zhikong scallop (Chlamys farreri) - Jiwen Chen; Wei Chen; Yifan Qu; Xiaoxue Lin; Haikun Zhang; Jilv Ma; Jie Cui; Fengchen Liu; Zhongyi Chu; Yue Zhao; Yabin Wang; Yaqiong Liu; et al. (Aquaculture, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Spin valve effect in hybrid spin filters with Cr2Ge2Te6 - Xiaoyu Wang; Shuxi Wang; Ying Zhang; Yi Ding; Xueyan Dong; Lin Zou; Shaojie Liu; Miao He; Takashi Taniguchi; Kenji Watanabe; Xuan Pan; Lei Zhang; et al. (Science Bulletin, 2026)

Numerical study on the leakage characteristic of the damaged LNG carrier in different wind scenarios - XinLong Zhang; QingYi Qu; Simone Mancini; Li Lin; YiHua Su; RenQing Zhu (Ocean Engineering, 2026)

Synthesis and leaching evaluation of entropy-stabilized zirconolite Ca(Zr,Hf,Sn)xTi3-xO7 (x = 0.8–2.2) - Qu Ai; Shi-Kuan Sun; Yu Tian; Wei-Dong Xiao; Yi Zhao; Sheng-Heng Tan; Wei-Ming Guo; Hua-Tay Lin (Chemical Engineering Journal, 2026)

A novel combined Enzymatic-Thermal hydrolysis process for mass reduction and resource recovery from waste activated sludge - Lin Li; Heyuan Lv; Lequn Qu; Xueqing Shi (Bioresource Technology, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

Sub-metre surface water mapping using Sentinel-1/2 with integrated super-resolution and deep learning - Jie Song; Jinyan Tian; Lin Zhu; Bingfeng Zhou; Xinyuan Qu; Che Wang; Niu Luo; Zhenxin Zhang; Lin Guo; Mingliang Gao; Xiaojuan Li; Huili Gong (International Journal of Remote Sensing, 2025)

Impact of protist predation on bacterial community traits in river sediments - Qiaojuan Wang; Linhao Zhang; Hui Lin; Jie Mao; Yaohui Bai; Chengzhi Hu; Jiuhui Qu (Water Research, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Unraveling the mechanistic interplay of carbon cycle and nitrogen transport within deep reservoirs: A perspective of δ13CDIC analysis - Yufei Bao; Yuchun Wang; Qian Zhang; Xiaobo Liu; Peng Hu; Meng Sun; Xiaodong Qu; Jie Wen; Shanze Li; Bing Lin; Jialong Huang (Journal of Hydrology, 2025)

Polychlorinated biphenyls-153 induces fat accumulation and lifespan shortening through CYP450 family genes in Caenorhabditis elegans - Zhi Qu; Panpan Wang; Yalu Wang; Peisen Guo; Guimiao Lin; Peixi Wang; Zengli Yu; Nan Liu (Journal of Environmental Sciences, 2025)

Microplastics as vectors for microcystin-LR: Enhanced bioavailability, oxidative damage, and immune dysregulation in zebrafish spleen - Wang Lin; Xixun Zhou; Yunyun Zeng; Xiaojie Li; Fufa Qu; Jianzhou Tang (Fish & Shellfish Immunology, 2025)

A newly identified homolog of scallop caspase-3/7 plays a pivotal role in the immunological response and orchestrates the induction of apoptosis - Jie Cui; Dianzhi Yao; Haikun Zhang; Yifan Qu; Xiaoxue Lin; Yaqiong Liu; Yijing Han; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2025)

A comprehensive overview of the composition, isolation, purification, and biological activities of abalone polysaccharides - Qing Zhang; Ling Qin; Jiayi Liu; Jinzheng Wei; Junhan Cao; Kai Wang; Mengke Yao; Huan Lin; Yingying He; Changfeng Qu; Jinlai Miao (Food and Bioproducts Processing, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

PANoptosis-related genes in the prognosis and immune landscape of hepatocellular carcinoma - Xiaowu Wang; Liangchen Qu; Zhikai Wen; Zhixuan Wu; Yuxiang Xue; Xuejia Yang; Ziwei Yuan; Yangyang Guo; Xingcheng Lin (Immunologic Research, 2025)

Eukaryotic expression and characterization of two α1,2-fucosyltransferase genes in the histo-blood group antigens synthesis pathway of the Pacific oyster (Crassostrea gigas) - Junxia Hu; Meng Qu; Weiran Zhang; Binbin Gui; Yanhua Jiang; Lin Yao; Shixin Wang; Dapeng Wang (Glycoconjugate Journal, 2025)

Population Genomics and Climate Change Vulnerability in Two Sympatric Desert Rodents - Tian Tian; Jilong Cheng; Yu Zhang; Lin Xia; Yilin Chen; Fangyuan Yang; Zhixin Wen; Yaqian Cui; Weibo Wang; Xueying Zhang; Yanhua Qu; Qisen Yang (Global Change Biology, 2025)
Climate change poses a severe threat to desert ecosystems; however, understanding how specialized desert species respond to changing climate remains limited. These species are confronting extreme changes, including intensified droughts, altered precipitation, and temperature patterns. Here, we integrate population and ecogenomic approaches to examine population genetic structure, demographic history, and climate adaptation in two distantly related, sympatric rodent species in arid and semi‐arid regions in East Asia. We further combine genomic offset analysis, ecological niche modeling, and landscape connectivity assessments to evaluate their climate change risks. Our results reveal that the two species have diverged into five geographically distinct lineages, each associated with a different arid region. Lineage divergence times are estimated between 20 and 400 thousand years ago, with population size declines occurring around the Last Glacial Maximum. While the two species exhibited distinct climate adaptation, evidenced by different key climatic variables and associated genes identified for each species, they exhibited congruent vulnerability to future climate change. This was indicated by parallel patterns of genomic offset and niche suitability loss. Under future climate change scenarios, eastern lineages in high precipitation seasonality areas (e.g., DB lineages in Horqin Sandy Land) face a higher risk due to substantial genomic offset, habitat loss, and reduced connectivity. In contrast, lineages on the west ranges with low precipitation seasonality (e.g., QH lineages in the Qaidam Basin and HL lineage in the Changtang Plateau) appear less vulnerable, characterized by lower genomic offset and the expansion of desert habitats. Overall, this study provides a comprehensive framework for identifying vulnerable populations and predicting responses to climate changes in desert species, offering critical insights for the conservation of desert ecosystems.

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Usage patterns and system dynamics of car-sharing in Chinese cities: Insights from a data-driven framework - Hongjie Wang; Xia Luo; Junfeng Chen; Qiming Su; Yaodong Wang; Shifeng Gong; Lin Qu (Sustainable Cities and Society, 2025)

Ensemble atomic sites for acidic oxygen evolution: mechanisms, atomic engineering, and AI-assisted screening - Wenjia Qu; Xingen Lin; Handuo Zheng; Jianuo Liu; Cheng Qian; Kong Chen; Huang Zhou; Yafei Zhao; Quan-Hong Yang; Yuen Wu (Science Bulletin, 2025)

Biocontrol potential and antifungal mechanism of a novel Bacillus velezensis NH-13–5 against Botrytis cinerea causing postharvest gray mold in table grapes - Lin Xiao; Jin-Tian Wang; Dong-Fang Cao; Hong Li; Hong-Yu Fang; Tian-Li Qu; Bao-Hua Zhang; Shuai-Shuai Li; Feng-Yu Du (Postharvest Biology and Technology, 2025)

Qualitative and quantitative detection of Zn2+ in food: design, synthesis and characterization of a near-infrared probe with large Stokes shift - Shizhen Wang; Xin Wang; Wenhui Xue; Yi Huo; Mengyu Chen; Cuibing Bai; Qixiang Song; Chenxu Liu; Lin Zhang; Changqing Qu; Hui Miao; Rui Qiao (Food Chemistry, 2025)

Mechanical properties of waterbomb origami tubes with enhanced energy absorption and crushing efficiency - Xiang Jie Wei; Yi Zhang; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Xiao Ji; Tao Ding; Jia Hui Zhang; Lin Hua; Wei Shen; Xin Ren (Engineering Structures, 2025)

Synergistic cation-anion interface engineering for uniform zinc deposition and stress mitigation in reinforced Zn metal anodes - Yixing Fang; Ping Li; Feng Sun; Chuyuan Lin; Xiao Yang; Zhen Wang; Guodong Miao; Lingxing Zeng; Yongchang Liu; Xuanhui Qu (Chemical Engineering Journal, 2025)

An amino functionalized iron based biochar for enhanced remediation for lead and lanthanum co-contaminated soil: Stress alleviation and stabilization mechanism - Fuxuan Bi; Zhao Jiang; Shuai Shi; Jia Qi; Mengning Wang; Qiutong Lin; Lei Wang; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

Divergent responses of ecological functions to long-term herbivore exclusion in the Tibetan mountainous grasslands - Shuaihao Bai; Jingxue Zhao; Guangpeng Qu; Lihua Tian; Gao-Lin Wu (Agriculture, Ecosystems & Environment, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Simultaneous doping of anions and cations to construct an internal electric field to promote photocatalytic activity - Tongtong Guan; Ran Chen; Yijun Wu; Xiantuo Chen; Jili Wen; Huanan Wang; Le Chen; Yingsu Qu; Mengyuan Hu; Jiang Wu; Jia Lin (Journal of Environmental Chemical Engineering, 2025)

Amphiphilic block copolymer-based fire suppression material – Study on coal spontaneous combustion prevention and extinguishing performance - Gang Zhou; Hongrui Qu; Bo Wei; Tianrui Niu; Yongmei Wang; Xiaosu Dong; Rulin Liu; Lin Li; Shuailong Li (Journal of Environmental Chemical Engineering, 2025)

Detoxifying zinc oxide nanoparticles during sludge anaerobic digestion in the presence of polyferric sulfate - Yongkui Yang; Junxiang Huang; Sen Qu; Guangxue Wu; Yiwen Liu; Yifeng Ling; Peizhe Sun; Yingxin Zhao; Lin Zhao (Journal of Environmental Chemical Engineering, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Smartphone-assisted ultrasensitive colorimetric strategy based on Cu-CN single-atom nanozyme for acrylamide detection in fried food - Jia Ge; Xiaoyu Sun; Xinxin Li; Yu Yang; Lin Zhang; Lingbo Qu; Zhaohui Li (Food Chemistry, 2025)

Characterization of SiIκB confirms the existence of a conserved IκB–NF-κB regulatory mechanism in sea urchin Strongylocentrotus intermedius - Yifan Qu; Yan Gao; Jie Cui; Haikun Zhang; Fengchen Liu; Xiaoxue Lin; Zhongyi Chu; Yaqiong Liu; Yijing Han; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2025)

Ball milling boron-doped biochar-based zero-valent iron composite for the removal of Cr(VI) from contaminated farmland: Performance and mechanisms - Hui Zhang; Yingrui Hu; Qiutong Lin; Wenqi Zhang; Siqi Wang; Haoming Li; Ruihan Tong; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

Integrated core-shell structured dual-mode thermoresponsive optical-electrical sensing fiber for accurate temperature recognition and early fire warning - Hualing He; Jie Xu; Md Hasib Mia; Zhonghe Yu; Yuhang Wan; Qing Jiang; Xueru Qu; Jinru Liu; Lin Hou; Yueyue Song; Zhicai Yu (Chemical Engineering Journal, 2025)

A GTPase activating protein Polrg1 regulates the development and cellulase expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Lin Xu; Ziyin Xu; Yihang Qu; Yu Wang; Chunna Sun; Mei Chen; Zhonghai Li (World Journal of Microbiology and Biotechnology, 2025)

Epidemiological characteristics and clinical treatment of melioidosis: a 11-year retrospective cohort study in Hainan - Tianzhou Lan; Guangqiang Zhao; Haichao Liu; Lei Qu; Qingjia Chi; Beibei Meng; Juan Fang; Fang Yang; Zhenhong Hu; Bin Wang; Rong Lin; Chenlong Rao; et al. (Infectious Diseases, 2025)

The regulatory role of DELLA protein DkGAI1 in persimmon dwarfism - Xialin Ye; Xinyi Yu; Hongcheng Liu; Xinxin Lin; Xuting Wu; Jiangtao Yu; Shenchun Qu (Plant Science, 2025)

Detrital zircon U Pb geochronology of the Cenozoic succession in the southern Tarim Basin: Implications for the northward expansion of the West Kunlun Orogen and the evolution of intracontinental convergence in the northwestern Tibetan Plateau - Chunyang Li; Kaixuan An; Xiubin Lin; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Shujun Liang; Xiaochun Wei; Yang Qu; Xinyue Zhao; Jialun Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Simultaneous monitoring of displacement and rotation of a long-span bridge based on innovative integration of GNSS and accelerometer measurements - Xuanyu Qu; Xiaoli Ding; You-Lin Xu (Engineering Structures, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Quality valuation and open fermentation process of polyhydroxyalkanoates production for the waste carbons biorefinery using Paracoccus sp. TOH as chassis - Leizhen Zhao; Lin Chen; Yuanxi Zhang; Jiexuan Han; Gaojie Sun; Jianhang Qu (Biomass and Bioenergy, 2025)

Complex spatiotemporal heterogeneity in Holocene human activities revealed by pollen and Pb records from major monsoonal China - Xiaoxu Qu; Zhiguo Rao; Zhongwei Shen; Yunxia Li; Lin Zhao; Chao Huang (Anthropocene, 2025)

Aggressive behavior recognition and welfare monitoring in yellow-feathered broilers using FCTR and wearable identity tags - Hongcheng Xue; Jie Ma; Yakun Yang; Hao Qu; Longhe Wang; Lin Li (Computers and Electronics in Agriculture, 2025)

Simulating vegetation potential and quantifying uncertainty for precision forestation in arid regions - Jia Qu; Zirui Gai; Qi Liu; Dongwei Gui; Xinlong Feng; Jianping Zhao; Tao Lin; Yunfei Liu; Qian Jin; Zeeshan Ahmed (Remote Sensing Applications: Society and Environment, 2025)

Dynamic changes of rice sheath non-structural carbohydrates and source-sink balance under elevated atmospheric CO2 concentration and temperature stresses - Hao He; Jiabin Shi; Mingjie Chen; Jing Zhao; Kexi Qu; Man Li; Lin Zhao; Yuanyuan Wang; Zhenghua Hu; Qi Li (Journal of Plant Physiology, 2025)

Organ-specific lithium accumulation and its toxic effects on female reproduction - Qigang Fan; Yi Sun; Qingjun Shen; Yuxin Wang; Jisheng Nie; Yanbing Lin; Shuaishuai Xing; Yan Li; Benhong Xu; Jianjun Liu; Xiaoting Shen; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Genomic insights into the brooding reproduction and climate-driven dynamics of Pocillopora damicornis in the Anthropocene - Jie Li; Yali Liu; Zhixin Zhang; Yu Chen; Jian Zhang; Haiyan Yu; Yingyi Zhang; Cong Liu; Zhuang Shao; David G. Bourne; Meng Qu; Si Zhang; et al. (Science China Life Sciences, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

A Rho-Type GTPase Protein Pocdc42 Regulates the Development and Cellulase Expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Ziyin Xu; Lin Xu; Yu Wang; Yihang Qu; Chunna Sun; Mei Chen; Zhonghai Li (Current Microbiology, 2025)

The combination of FLI, ITS, pFF, and citrate improves the developmental potential of gilt oocytes during in vitro maturation - Zhilong Chen; Caiyong Zhang; Chao Yan; Cuiting Peng; Hao Xie; Yingting Pan; Lin Qi; Chaoqun Qu; Yulan Zhao; Zhonglin Tang (Animal Reproduction Science, 2025)

Habitat‐Forming Species: Buffers or Amplifiers for Mutualistic Organisms in Response to Climate Change? - Junmei Qu; Zhixin Zhang; Shaobo Ma; Yaqi Wang; Xiaoyu Tang; Jianping Yin; Geng Qin; Qiang Lin (Journal of Biogeography, 2025)
Aim Habitat‐forming species play a critical role in coral reef ecosystems by creating complex physical structures for marine species. Driven by climate change, these habitat‐forming species are undergoing considerable shifts in their geographical distribution, which might trigger cascading effects via protection mutualisms, leading to alterations in the relationships between species. We examined the role of habitat‐forming species in regulating spatial distributions of their mutualistic protectors' influence. Location Global coastal ocean. Methods We used species distribution models to examine how suitable habitats for organisms that form mutualistic relationships with habitat‐forming species respond to climate change, focusing on two representative macrosymbiotic relationships in coral reefs: Coral–coral crab and sea anemone–clownfish. Results The results revealed that corals are more sensitive to climate change than sea anemones, experiencing greater range contractions under projected future conditions. Consequently, the distribution ranges of both coral‐mutualistic crabs and sea anemone‐mutualistic clownfishes are expected to reduce even further when protection mutualisms are considered. Coral crabs are projected to undergo a more rapid range size loss than clownfishes. Main Conclusion These findings highlight the importance of incorporating interspecific interactions among habitat‐forming species into predictions of potential shifts in the biogeographic distributions of mutualistic protectors under climate change.

Differences in predictions of marine species distribution models based on expert maps and opportunistic occurrences - Zhixin Zhang; Jamie M. Kass; Ákos Bede‐Fazekas; Stefano Mammola; Junmei Qu; Jorge García Molinos; Jiqi Gu; Hongwei Huang; Meng Qu; Ying Yue; Geng Qin; Qiang Lin (Conservation Biology, 2025)
Species distribution models (SDMs) are important tools for assessing biodiversity change. These models require high‐quality occurrence data, which are not always available. Therefore, it is increasingly important to determine how data choice affects predictions of species’ ranges. Opportunistic occurrence records and expert maps are both widely used sources of species data for SDMs. However, it is unclear how SDMs based on these data differ in performance, particularly for the marine realm. We built SDMs for 233 marine fish species from 2 families with these 2 occurrence data types and compared their performances and potential distribution predictions. Opportunistic occurrences were sourced from field surveys in the South China Sea and online repositories and expert maps from the International Union for Conservation of Nature Red List database. We used generalized linear models to explore drivers of differences in prediction between the 2 model types. When projecting to distinct regions with no occurrence data, models calibrated using opportunistic occurrences performed better than those using expert maps, indicating better transferability to new environments. Differences in marine predictor values between the 2 data types accounted for the dissimilarity in model predictions, likely because expert maps included large areas with unsuitable environmental conditions. Dissimilarity levels among fish families differed, suggesting a taxonomic bias in biodiversity data between data sources. Our findings highlight the sensitivity of species distribution predictions to the choice of distributional data. Although expert maps have an important role in biodiversity modeling, we suggest researchers assess the accuracy of these maps and reduce commission errors based on knowledge of target species.

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Pivotal roles of intracellular Cl− in COVID-19: pathogenesis and therapeutic targets - Su Qu; Lei Chen; Jie Sheng; Xiao-Chun Hou; Wen-Liang Zhou; Nan-Shan Zhong; Yi-Lin Zhang (Science Bulletin, 2025)

Elevational amplification of plateau pika (Ochotona curzoniae) burrowing impacts on ecological functions in alpine grasslands - Guangpeng Qu; Jingxue Zhao; Gao-Lin Wu (Journal of Environmental Management, 2025)

Integrated core-shell structured polyimide thermoelectric fiber with latent light-driven damage detection and self-driven temperature sensing performance - Zhicai Yu; Xueru Qu; Mi Zhou; Md Hasib Mia; Lin Hou; Yudong Wang; Jie Xu; Lele Huang; Liulu Zhang; Qianyu Zeng; Hualing He (Chemical Engineering Journal, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

Effects of ambient temperature on heart rate and blood oxygen saturation in sedentary people - Jiqing Qu; Tianyu Lin; Qingcheng Lin; Xuefeng Li; Hui Xiao (Building and Environment, 2025)

Compliance assessment oriented microcystin prediction: A Bayesian adaptive LASSO Tobit quantile regression approach - Fan Qu; Lingjing Lin; Changbo Qin; Fuli Peng; Runzi Wang; Nengwang Chen; Gang Zhao; Wentao Lu; Zhongyao Liang (Algal Research, 2025)

Heavy metal contamination in fish and human health risks from lakes of a mega inter-basin water diversion - Wenxia Fan; Wentong Xia; Lian-Shin Lin; Han Liu; Xiao Qu; Wei Xin; Lizhou Tang; Yushun Chen (Chemosphere, 2025)

Transcription factor FOXD3 participates in the immune response of Pinctada fucata martensii by regulating nAChR-5 - Min Yang; Yongge Huang; Xinyi Lin; Zhihan Li; Shilin Zheng; Youmei Qu; Yue Wen Deng; Ronglian Huang; Yu Jiao (Aquaculture, 2025)

Significance of temperature and salinity in the dynamics of diatoms and dinoflagellates along the coastal Yellow Sea - Chenshi Weng; Dongsheng Ding; Qian Yang; Lin Zhu; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Progress in Oceanography, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Strategy for enhanced soil lead passivation and mitigating lead toxicity to plants by biochar-based microbial agents - Shuqi Wei; Xiaoyang Liu; Yue Tao; Xintong Wang; Zheen Lin; Yupeng Zhang; Qi Hu; Lei Wang; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2025)

Evolved size-specific dose estimates for patient-specific organ doses from chest CT scans based on hybrid patient size vectors - Wencheng Shao; Ke Yang; Lizhi Lou; Xin Lin; Liangyong Qu; Weihai Zhuo; Haikuan Liu (Physical and Engineering Sciences in Medicine, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

High-pressure Raman spectroscopy of Al-rich and pure-Mg phase D - Chaowen Xu; Li Zhang; Xiaofeng Lu; Yanhao Lin; Shuo Qu; Shuchang Gao; Fengxia Sun; Ying Li (Physics and Chemistry of Minerals, 2025)

Corrigendum to “Redistribution of vocal snapping shrimps under climate change” [Sci. Total. Environ. 954 (2024) 176191] - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2025)

Quantum cooling engine fueled by quantum measurements - Dengke Qu; Kunkun Wang; Lei Xiao; Zhongliang Wang; Xiang Zhan; Haiqing Lin; Peng Xue (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comparative assessment of coke and petroleum coke as potential electrode materials in constructed wetlands-microbial fuel cells - Xueting Zhang; Jingjing Du; Mingxiang Qu; Maosen Wang; Kexin Lin; Xin Jiang; Zengzhi Qin; Chenchao Wang; Jianguo Zhao; Baodan Jin; Xia Cao; Yuanqian Xu (Journal of Water Process Engineering, 2025)

Effects of cultivation on soil carbon and nitrogen along an altitudinal gradient in the Southeastern Tibetan Plateau - Haojing Lei; Fengzi Li; Xu-Ri; Songbo QU; Ribu Shama; Lin Zhang; Eryuan Liang (Forest Ecology and Management, 2025)

Perovskite quantum dots Revolutionize Lithium-Sulfur battery Performance: Cathode catalytic Breakthrough with CsPbBr3 - Renjing Duan; Xiaoshi Lang; Xiang Wang; Lan Li; Tingting Qu; Lin Wang; Jianbin Li; Chuangang Yao; Kedi Cai (Chemical Engineering Journal, 2025)

Genome-wide identification and functional characterization of the Shaker potassium channel family in centipedegrass suggest their distinct roles in potassium uptake and salt tolerance - Dong-Li Hao; Jin-Yan Zhou; Jia Qu; Jun-Yi Zhai; Ying Zhao; Jian-Xiu Liu; Hai-Lin Guo; Jun-Qin Zong (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Advances in Neuroprotective Mechanisms of Aerobic Exercise to Reduce the Risk of Glaucoma - Yaqian Qu; Jingquan Sun; Lin Li; Siyu Chen; Yihan Ni; Xiangdeng Lai; Wang Yi (Journal of Science in Sport and Exercise, 2025)

The Phytoplankton Community Exhibited Restored Species Diversity but Fragile Network Stability Under Potential Sustainable Aquaculture Approach of Marine Ranching - Dongqun Wei; Zeping Xie; Jialin Li; Diansheng Ji; Lin Qu; Baoquan Li; Xiao Wei; Song Qin (Journal of Marine Science and Engineering, 2025)
Mariculture is currently experiencing rapid growth in response to the rising global food demand, while simultaneously posing significant challenges to environmental issues, such as pollution stress and ecological degradation. To achieve a balance between ecosystem maintenance and seafood supply, marine ranching has flourished as a sustainable approach through the implementation of artificial reef construction, stock enhancement, and strategic releasing. However, few studies have evaluated the ecological impacts through a comparison of in situ survey data across geographical areas. Phytoplankton are vital organisms in marine ecosystems that function as essential indicators of seawater quality and biological diversity, reflecting environmental health and ecological sustainability. In this study, we investigated the species diversity, community structure, and co-occurrence network of phytoplankton based on 175 samples collected from 75 sites encompassing all 26 marine ranching seawater areas, along with their corresponding surrounding areas in Yantai’s coastal sea. A total of 112 species were identified across three phyla of diatoms, dinoflagellates, and chrysophytes; among them, diatoms dominated the community with a notably high proportion of 98.83%. Their diversity and structure exhibited significant variations across different seasons and geographic locations. Moreover, no preference was observed between the marine ranching seawater and the surrounding areas. Nevertheless, a co-occurrence network analysis demonstrated that lower values for average degree, clustering coefficient, and average path length were exhibited in marine ranching, indicating that aquaculture activities have reduced connectivity among potential interactions. Additionally, it showed reduced stability as indicated by the remaining nodes and the natural connectivity indices, regardless of the proportion of nodes removed. These findings illustrate that while marine ranching processes can mitigate species losses with maintaining phytoplankton community structure, they still alter association among species and reduce overall stability. This research recommends that scientifically informed expansion of marine ranching necessitates robust environmental monitoring datasets and systematic validation to ensure holistic sustainability.

Individual and mixed associations between fine particulate matter components and hospital admissions for hypertension: Insights from a large-scale South Chinese cohort study - Yuqin Zhang; Jing Wei; Shirui Chen; Tarik Benmarhnia; Kai Zhang; Xiaowen Wang; Xinlei Deng; Haogao Gu; Ziqiang Lin; Yanji Qu; Jianpeng Xiao; Jie Jiang; et al. (Sustainable Cities and Society, 2025)

Potential genetic markers of biofilm formation ability by Listeria monocytogenes isolated from fresh agricultural products - Jing Wang; Qingli Dong; Xiujin Chen; Bo Feng; Yang Qu; Ting Lin; Yalong Bai; Peihong Liu; Changyan Zhou; Yujuan Suo (International Journal of Food Microbiology, 2025)

Modulation of CO2 hydrogenation selectivity through microstructural phase evolution-induced electronic transfer on Ni/TiO2 - Yunhao Zang; Xuetan Lin; Jiangying Qu; Feng Gao; Jianfeng Gu; Taipeng Wei; Rongrong Wang (Fuel, 2025)

Progress in separation and detection of foodborne bacteria for food safety - Lei Wang; Kaiyuan Jia; Xiaoyun Qu; Yanbin Li; Jianhan Lin (Current Opinion in Food Science, 2025)

Recent advances in antibiotic removal using independent and coupled microbial fuel cells (MFCs): Mechanisms and cells (MFCs): Mechanisms and practical applications - Liye Liang; Yingzi Lin; Ruijun Ren; Qingjing Zhang; Jiangqi Qu; Yuanhao Liu; Zhe Han; Xin Sun (Journal of Water Process Engineering, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

Evaluating complementaries among urban water, energy, infrastructure, and social Sustainable Development Goals in China - Ke Yu; Yifan Song; Jin Lin; Shen Qu (Journal of Environmental Sciences, 2025)

NF-κB inhibitor PDTC involved in regulating the transplantation immunity in the pearl oyster Pinctada fucata martensii - Shirong Fu; Xinyi Lin; Xiaowen Lu; Youmei Qu; Hongxi Chen; Shilin Zheng; Zhihan Li; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

Application of nail analysis in human biomonitoring of toxic pollutants: A review - Zhuowen Li; Yanji Qu; Meiqing Lin; Yingxin Yu; Shengtao Ma (Environmental Pollution, 2025)

Enhancing membrane distillation performance by adsorption using modified zeolite for shale gas produced water treatment - Haiqing Chang; Lin Huang; Mengzhe Lu; Zhongsen Yan; Pengwei Ji; Dan Qu; Fangshu Qu; Heng Liang (Desalination, 2025)

High-speed atomic force microscopy reveals opposite traffic of processive chitinases impairs α-chitin biodegradation - Mingbo Qu; Lin Kong; Pengfei Li; Aijing Zhang; Toshio Ando; Qing Yang (Carbohydrate Polymers, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Membrane-covered aerobic composting mitigated nitrous oxide emission through improved micro-aerobic state and enhanced carbon source utilization - Jinpeng Xiong; Huiwen Qu; Mary Harty; Shuguang Lin; Guangqun Huang (Bioresource Technology, 2025)

Underlying the early signaling and gene expression of Pleurotus ostreatus mycelia during injury response - Jiachun Zhu; Jiaqi Sun; Huiping Li; Ping Xu; Lin Ma; Qiang Wang; Keping Chen; Shaoxuan Qu (World Journal of Microbiology and Biotechnology, 2025)

The dark activity of Arabidopsis blue-light receptor CRY2 - Gao-Ping Qu; Zeru Zhang; Chentao Lin (Science China Life Sciences, 2025)

Potential causal links of long-term PM2.5 components exposure with diabetes incidence and mortality in the United States - Gonghua Wu; Shenghao Wang; Wenjing Wu; Tarik Benmarhnia; Shao Lin; Kai Zhang; Xiaobo Xue Romeiko; Haogao Gu; Yanji Qu; Jianpeng Xiao; Xinlei Deng; Ziqiang Lin; et al. (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In situ sulfur-loaded on carbon materials for efficient antibiotic removal under visible light - Shouxin Zhu; Zhexiao Zhu; Jingyi Qu; Can Sun; Zijie Fang; Mingli Qin; Yangben Chen; Xiaolu Xu; Jiahui Lin; Min Liu; Hui Zheng (Journal of Water Process Engineering, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Testing and improving brGMGTs-based paleotemperature estimates in peat sediments: Evidence from global surface peat samples and two well-dated Holocene peat cores in far Northwest China - Zhongwei Shen; Minghua Zhao; Tianyan Lin; Xiaoxu Qu; Haichun Guo; Jiantao Cao; Guodong Jia; Zhiguo Rao (Global and Planetary Change, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Immuno- and gut microbiota-modulatory activities of β-1,6-glucans from Lentinus edodes - Xian Qu; Yahui Ji; Jieyi Long; Donglin Zheng; Zhonghui Qiao; Yue Lin; Chang Lu; Yifa Zhou; Hairong Cheng (Food Chemistry, 2025)

Mechanical properties of a novel fiber-bridging interface for connecting FRP profile and concrete - Hongwei Lin; Haidong Qu; Peng Feng; Huixin Zeng; Guanzhi Cheng (Engineering Structures, 2025)

Lysosomal cation channel TRPML1 suppression sensitizes acute myeloid leukemia cells to chemotherapeutics by inhibiting autophagy - Meifang Dai; Bingqian Lin; Hao Li; Youming Wang; Miaomiao Wu; Yanan Wei; Wenping Zeng; Lili Qu; Chunlei Cang; Xingbing Wang (Molecular and Cellular Biochemistry, 2025)

Integrating sentinel-2a imagery, DEM data, and spectral feature analysis for landslide detection via fully convolutional networks - Yu Qu; Hanfa Xing; Lin Sun; Xian Shi; Jianfeng Huang; Zurui Ao; Zexiu Chang; Jiaju Li (Landslides, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Construction of a high-resolution city-level emission inventory based on multiple methods: a case study of Cangzhou City, China - Xin Bo; Wanyue Shan; Jiabao Qu; Tuantuan Lei; Minjie Sang; Zhaoling Li; Aijun Lin (Environment, Development and Sustainability, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Pyramid-Matrix-like buried interface construction for Boosting the photovoltaic performance of perovskite solar cells - Xin Luan; Ying Han; Mengyao Sun; Yingjie Wang; Le Zhang; Yuhuan Song; Fengyou Wang; Lin Fan; Xin Qu; Xiaoyan Liu; Lili Yang (Chemical Engineering Journal, 2025)

Auriculasin induces mitochondrial oxidative stress and drives ferroptosis by inhibiting PI3K/Akt pathway in non-small cell lung cancer - Xiaodong Wang; Tao Zhang; Lin Qu; Yifan Zhang; Guizhou Gao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

High-rate bridge displacement monitoring with low-rate virtual reference station data - Xuanyu Qu; Xiaoli Ding; Wenkun Yu; Xinrui Li; You-Lin Xu (GPS Solutions, 2025)
We present a new Global Navigation Satellite Systems (GNSS) positioning approach that utilizes low-rate Virtual Reference Station (VRS) data to achieve high-rate displacement monitoring. The method integrates tightly the VRS technology with asynchronous Real-Time Kinematic (RTK) method to overcome the limitation of VRS in high-rate structural health monitoring (SHM) applications. When this approach is used, no local reference station is required so that the efforts and cost of setting up reference stations can be avoided. Experiments with datasets from a controlled shaking platform and a long-span bridge in Hong Kong with both temperature and typhoon excitations have indicated that the proposed approach worked effectively. The results demonstrated that when a baseline exceeded about 3 km, the vertical errors of RTK GNSS positioning could be up to about 15.9 mm (standard deviations), insufficient for most SHM applications. In this case, the proposed method enhanced the accuracy by about 60% to 6.0 mm when using VRS data openly available in Hong Kong. The accuracy achieved was equivalent to that of RTK positioning using a 1.2 km baseline. The shaking platform trial demonstrated that the monitoring station could be up-sampled to 100 Hz without a noticeable loss in accuracy. The proposed method could capture precisely the peak frequencies and amplitudes of vibrations, with errors as low as 0.001 Hz and 0.1 mm. This method broadens the applicability of GNSS positioning in SHM applications.

Redistribution of vocal snapping shrimps under climate change - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2024)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Optical characteristic of dissolved organic matter polar fractions by spectrum technologies and the relationship with indirect photodegradation of ofloxacin - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Qingjing Hu; Yuqiu Wei; Lin Zhu; Keming Qu; Rongguo Su (Journal of Environmental Chemical Engineering, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

Plant oil-based phase change materials for sustainable thermal energy storage: A review - Wen-Ya Wu; Ming Gao; Reuben Yeo Jueyuan; Ming Lin; Suxi Wang; Warintorn Thitsartarn; Xikui Zhang; Dan Kai; Pei Wang; Zhenyao Qu; Jianwei Xu; Xian Jun Loh; et al. (Fuel, 2024)

Reduced Proteolipid Protein 2 promotes endoplasmic reticulum stress-related apoptosis and increases drug sensitivity in acute myeloid leukemia - Fahui Xie; Jia Qu; Dainan Lin; Kexin Feng; Mingzhu Tan; Haixiu Liao; Longhui Zeng; Qingquan Xiong; Jun Huang; Weiwen Chen (Molecular Biology Reports, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Gastrodin ameliorates diabetic nephropathy by activating the AMPK/Nrf2 pathway - Shuqin Zhao; Qingyun Pan; Xiaolin Lin; Xian Li; Li Qu (Journal of Molecular Histology, 2024)

Spotlight on the accumulation of heavy metals in Traditional Chinese medicines: A holistic view of pollution status, removal strategies and prospect - Yan Liu; Kangzhe Fu; Aijing Leng; Lin Zhang; Jialin Qu (Science of The Total Environment, 2024)

Comparison of prenatal and postnatal exposure to neonicotinoids and their temporal trends in breast milk - Kaiqin Huang; Meiqing Lin; Jing Yi; Guocheng Liu; Rui Hua; Yangyang Liu; Yanji Qu; Cairong Chen; Shengtao Ma (Science of The Total Environment, 2024)

Copper-based photocatalysts with natural organic ligands for efficient removal of tetracycline under visible light - Shouxin Zhu; Can Sun; Zhexiao Zhu; Jingyi Qu; Zijie Fang; Yangben Chen; Jiahui Lin; Xiaolu Xu; Miaoyan Cheng; Min Jiang; Hui Zheng (Journal of Environmental Management, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

The role of pattern recognition receptors in the innate immune system of Chinese mitten crab (Eriocheir sinensis) - Chenchen Shi; Ta-Hui Lin; Chen Qu (Fish & Shellfish Immunology, 2024)

The joint impact of PM2.5 constituents on the risk of cerebrovascular diseases hospitalization: A large community-based cohort study - Shirui Chen; Yuqin Zhang; Ziqiang Lin; Ruqing Liu; Lingling Zheng; Xiuyuan Chen; Shao Lin; Yanji Qu; Chun Hao; Hui Tang; Jing Wei; Wangjian Zhang; et al. (Environmental Research, 2024)

Occurrence of bisphenol analogues and their conjugated metabolites in foodstuff - Jianli Qu; Ruyue Guo; Lin Liu; Fangfang Ren; Hangbiao Jin (Science of The Total Environment, 2024)

The effect of cross-regional transport on ozone and particulate matter pollution in China: A review of methodology and current knowledge - Kun Qu; Yu Yan; Xuesong Wang; Xipeng Jin; Mihalis Vrekoussis; Maria Kanakidou; Guy P. Brasseur; Tingkun Lin; Teng Xiao; Xuhui Cai; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2024)

Protocatechuic acid enhanced Fe(III) activated peroxymonosulfate system for Sulfamethoxazole degradation in groundwater - Siqi Wang; Ran Wang; Qiutong Lin; Ruixin Liu; Xiaoyu Wu; Guangshan Zhang; Qi Hu; Zhao Jiang; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Algae promotes the biogenic oxidation of Mn(II) by accelerated extracellular superoxide production - Jing Qi; Xi Wang; Zemiao Lin; Jijin Zhao; Chengzhi Hu; Jiuhui Qu (Water Research, 2024)

Photochemical transformation of liquid crystal monomers in simulated environmental media: Kinetics, mechanism, toxicity variation and QSAR modeling - Yandong Yang; Xiangkun Jiang; Yi Yang; Jia Wang; Yahui Zhao; Shanshan Lin; Jiao Qu; Christopher J. Martyniuk; Yuanhui Zhao; Chao Li (Water Research, 2024)

13C evidence for the selective loss of active and inert organic carbon in soil aggregates under rain-induced overland flow erosion - Jiuqi Qu; Jinquan Huang; Lin Liu (Geoderma Regional, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Promoting bone regeneration with liquid crystal bone cement from a new perspective: Inhibiting BMSCs PANoptosis under aseptic inflammation - Shuyun Zhang; Dengjian Qu; Zhen Lin; Lihua Li; Changpeng Xu (Chemical Engineering Journal, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Colletotrichum cliviicola as a new causal agent causing leaf spot disease on Tilia tomentosa moench (silver linden) in China - Lin Chang; Xue-hai Li; Yi-lin Li; Zi-wen Gao; Yue-mei Zhang; Ning-Li; Zhao-lei Qu; Yi-hong Yang; Hui Sun (Crop Protection, 2024)

Corrigendum to “Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study” [Water Research 252 (2024) 12191] - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

Bacterial evolution in Biofiltration of drinking water treatment plant: Different response of phage and plasmid to varied water sources - Peijun Zhang; Yuhan Wang; Huan Lin; Jinsong Liang; Juntao Wang; Yaohui Bai; Jiuhui Qu; Aijie Wang (Water Research, 2024)

Northward expansion of the West Kunlun orogenic belt during the Cenozoic and its implications for the evolution of the northwest Tibetan Plateau: Constraints from sediment dispersal patterns in the Buya Basin, China - Shujun Liang; Xiubin Lin; Chunyang Li; Xiaochun Wei; Yang Qu; Kaixuan An; Cai Chen; Xianzhang Yang; Yong Li; Liang Zhang; Jiangwei Shang; Li Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Diffusion hysteresis in unsaturated porous media: A microfluidic study - Yajuan Zhuang; Guangfeng Zhu; Yiyang Jin; MingLiang Qu; Qingyang Lin; Lingzao Zeng (Journal of Hydrology, 2024)

Structural evolution in S-vacancy-rich Co@Co9S8 during selective benzyl alcohol electrooxidation reaction - Lei Huang; Xiongchao Lin; Jun Zhang; Caihong Wang; Sijian Qu; Yonggang Wang (Journal of Cleaner Production, 2024)

Smart windows based on ultraviolet-B persistent luminescence phosphors for bacterial inhibition and food preservation - Xiaohui Lin; Chonghui Li; Shicai Xu; Jihua Wang; Huanxin Yang; Yikai Qu; Qingshuai Chen; Zhenghua Li; Mengyu Su; Guofeng Liu; Hanping Liu; Jilei Yang; et al. (Food Chemistry, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Morphological convergence from independent crab lineages contributes to the flourishing symbiotic diversity between crabs and branching corals - Shaobo Ma; Zelin Chen; Yuli Sun; Meng Qu; Xin Wang; Wei Jiang; Geng Qin; Qiang Lin (Coral Reefs, 2024)

Inhibitory effect of ammonium conversion by deep nitrogen application effectively reduces gaseous nitrogen losses - Changhong Liu; Yanjie Qu; Changjie Feng; Yongqiao Zhang; Shiyu Li; Zhenhua Lei; Haowei Feng; Xiang Lin; Dong Wang (Agriculture, Ecosystems & Environment, 2024)

Disinfectant-induced ammonia oxidation disruption in microbial N-cycling process in aquatic ecosystem after the COVID-19 outbreak - Lutong Yang; Ping Han; Qiaojuan Wang; Hui Lin; Donglin Wang; Jie Mao; Weixiao Qi; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Nanoplastic pollution changes the intestinal microbiome but not the morphology or behavior of a freshwater turtle - Shuo Gao; Shufang Zhang; Jiahui Sun; Xinni He; Shaoshuai Xue; Wenyi Zhang; Peng Li; Longhui Lin; Yanfu Qu; Georgia Ward-Fear; Lian Chen; Hong Li (Science of The Total Environment, 2024)

Above- and belowground phenology responses of subtropical Chinese fir (Cunninghamia lanceolata) to soil warming, precipitation exclusion and their interaction - Zekun Qu; Chengfang Lin; Haiying Zhao; Tingting Chen; Xiaodong Yao; Xiaohong Wang; Yusheng Yang; Guangshui Chen (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Bioaccumulation of polycyclic aromatic hydrocarbons and their human health risks depend on the characteristics of microplastics in marine organisms of Sanggou Bay, China - Qi Sui; Xiaobin Yang; Xuemei Sun; Lin Zhu; Xinguo Zhao; Zhihua Feng; Bin Xia; Keming Qu (Journal of Hazardous Materials, 2024)

Battery recycling models selection and contractual incentives: From an information sharing perspective - Lin Feng; Mengru Qu; Adolf K.Y. Ng; Peng Jia; Haibo Kuang (Journal of Cleaner Production, 2024)

Enhanced antibacterial activity of bovine milk exosome-based drug formulation against bacterial pathogens - Qingjun Xu; Shuo Yang; Kai Zhang; Ying Liu; Lin Li; Shaoqi Qu (Food Chemistry, 2024)

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Moderate oxidation of algae-laden water: Principals and challenges - Xin Mao; Qingnan Wang; Haiqing Chang; Bin Liu; Shiqing Zhou; Lin Deng; Bing Zhang; Fangshu Qu (Water Research, 2024)

Environmental controls on the seasonal variations of diatoms and dinoflagellates in the Qingdao coastal region, the Yellow Sea - Qingxuan Wang; Qian Yang; Lin Zhu; Zhengguo Cui; Keming Qu; Yuqiu Wei (Marine Environmental Research, 2024)

Polysaccharides from Auricularia cornea var. Li.: Structural alterations during in vitro digestion and its potent immunomodulatory properties on macrophages - Nan Lin; Minmeng Li; Zixuan Han; Xiaojuan Liu; Jialin Qu; Xinhui Wang; Xuchang Duan; Caian He (Food Bioscience, 2024)

Unveiling the unique role of iron in the metabolism of methanogens: A review - Yuxin Ma; Ying Qu; Xiangwu Yao; Chujun Xia; Mengjie Lv; Xiao Lin; Lili Zhang; Meng Zhang; Baolan Hu (Environmental Research, 2024)

Exploring near-bottom turbulent mixing across the Challenger Deep based on temperature spectral analysis - Yuan-Zheng Lu; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Jian Lin; Xian-Rong Cen; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

DNA-AuNP encoders array Integrating a multi-modal coupled analysis approach for noninvasive precision screening of myocardial function injury disease in children - Haixia Zou; Wei Ye; Jienan Shen; Yahong Chen; Guangpei Qi; Lingzhi Ye; Lin Yang; Junjie Yuan; Yi Zeng; Hui Yang; Guangli Ren; Xiangmeng Qu (Chemical Engineering Journal, 2024)

Enhanced degradation of atrazine from soil with recyclable magnetic carbon-based bacterial pellets: Performance and mechanism - Jianhua Qu; Ziwei Li; Siqi Wang; Qiutong Lin; Zhiyu Zhang; Zhihuan Wu; Qi Hu; Zhao Jiang; Yue Tao; Ying Zhang (Chemical Engineering Journal, 2024)

Engineering ZIF-67 loaded nanofibrous membrane with thermal stabilization treatment for efficient photocatalytic CO2 reduction - Pengfei Lin; Xiwei Qu; Bhaskar Jyoti Deka; Chao Hu; Lei Zhao; Dongyun Wu; Chunhai Yi; Min Wei Boey; Muhammad Usman Farid; Alicia Kyoungjin An; Jiaxin Guo (Chemical Engineering Journal, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Landfill leachate treatment by direct contact membrane distillation: Impacts of landfill age on contaminant removal performance, membrane fouling and scaling - Zhimeng Yang; Songze Lin; Linxiong Ye; Dan Qu; Haiyang Yang; Haiqing Chang; Huarong Yu; Zhongsen Yan; Hongwei Rong; Fangshu Qu (Desalination, 2024)

Glucose-Responsive hydrogel optimizing Fenton reaction to eradicate multidrug-resistant bacteria for infected diabetic wound healing - Xingchen Li; Zifan Meng; Lin Guan; Annan Liu; Lei Li; Maja D. Nešić; Bai Yang; Wenrui Qu; Quan Lin (Chemical Engineering Journal, 2024)

An Improved Identification Method of Pipeline Leak Using Acoustic Emission Signal - Jialin Cui; Meng Zhang; Xianqiang Qu; Jinzhao Zhang; Lin Chen (Journal of Marine Science and Engineering, 2024)
Pipelines constitute a vital component in offshore oil and gas operations, subjected to prolonged exposure to a range of alternating loads. Safeguarding their integrity, particularly through meticulous leak detection, is essential for ensuring safe and reliable operation. Acoustic emission detection emerges as an effective approach for monitoring pipeline leaks, demanding subsequent rigorous data analysis. Traditional analysis techniques like wavelet analysis, empirical mode decomposition (EMD), variational mode decomposition (VMD), and complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) often yield results with considerable randomness, adversely affecting leak detection accuracy. This study introduces an enhanced damage recognition methodology, integrating improved complete ensemble empirical mode decomposition with adaptive noise (ICEEMDAN) and probabilistic neural networks (PNN) for more accurate pipeline leak identification. This novel approach combines laboratory-acquired acoustic emission signals from leaks with ambient noise signals. Application of ICEEMDAN to these composite signals isolates eight intrinsic mode functions (IMFs), with subsequent time–frequency analysis providing insight into their frequency structures and feature vectors. These vectors are then employed to train a PNN, culminating in a robust neural network model tailored for leak detection. Conduct experimental research on pipeline leakage identification, focusing on the local structure of offshore platforms, experimental research validates the superiority of the ICEEMDAN–PNN model over existing methods like EMD, VMD, and CEEMDAN paired with PNN, particularly in terms of stability, anti-interference capabilities, and detection precision. Notably, even amidst integrated noise, the ICEEMDAN–PNN model maintains a remarkable 98% accuracy rate in identifying pipeline leaks.

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

Advancing real-time error correction of flood forecasting based on the hydrologic similarity theory and machine learning techniques - Peng Shi; Hongshi Wu; Simin Qu; Xiaoqiang Yang; Ziheng Lin; Song Ding; Wei Si (Environmental Research, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Considering biotic interactions exacerbates the predicted impacts of climate change on coral‐dwelling species - Zhixin Zhang; Shaobo Ma; Ákos Bede‐Fazekas; Stefano Mammola; Meng Qu; Jinxin Zhou; Ellias Yuming Feng; Geng Qin; Qiang Lin (Journal of Biogeography, 2024)
Aim Climate change is affecting the geographic distributions of many species and researchers are increasingly relying on species distribution models (SDMs) to forecast species' redistributions under climate change. Such modelling studies, however, often ignore biotic interactions that shape species' geographic ranges. This is especially problematic for coral reefs, which host a high diversity of species and interactions. We tested how biotic interactions affect the distribution patterns of obligate coral‐dwelling Trapezia crabs. Location Global coastal ocean. Time Period 2000–2014, 2040–2050, 2090–2100. Major Taxa Studied Corals and coral‐dwelling Trapezia crabs. Methods We determined the symbiotic relationships between 22 crab species in the genus Trapezia and corals via field survey and extensive literature review. We first developed SDMs for coral and crab species using exclusively abiotic variables (abiotic‐only models for corals and crabs). Then we constructed a second set of models where we accounted for coral distributions into crab predictions by combining model predictions for the two taxa a posteriori (abiotic‐plus‐biotic models for crabs only). Results We obtained 30 commonly accepted coral‐crab symbiotic relationships from nine Trapezia crab and six stony coral species. The abiotic‐only model predictions showed that six corals may lose approximately one‐sixth of suitable ranges under RCP 8.5 in 2040–2050. The two types of models for crabs yielded largely different habitat suitability predictions and accounting for biotic interactions into SDM predictions exacerbates the predicted impacts of climate change on coral‐dwelling crabs. Main Conclusions Our results show large discrepancies in crab spatial distribution patterns with and without accounting for symbiotic interactions. Our findings highlight the important role of modeller's decision on accounting for biotic interactions when predicting the geographical ranges of coral‐dwelling species, with important implications for designing future conservation and management strategies for marine species.

Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

Integrated evidence of transcriptional, metabolic, and intestinal microbiota changes in Ruditapes philippinarum due to perfluorooctanoic acid-induced immunotoxicity - Fengling Li; Xiuqiong Gong; Yang Zhou; Qianqian Geng; Yanhua Jiang; Lin Yao; Meng Qu; Zhijun Tan (Science of The Total Environment, 2024)

Warming differentially affects above- and belowground ecosystem functioning of the semi-arid alpine grasslands - Jingxue Zhao; Wen Yang; Lihua Tian; Guangpeng Qu; Gao-Lin Wu (Science of The Total Environment, 2024)

Digitalizing river aquatic ecosystems - Yaohui Bai; Hui Lin; Chenchen Wang; Qiaojuan Wang; Jiuhui Qu (Journal of Environmental Sciences, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

Enlightening thermoelectric mastery: Bio-inspired cellulose gel containing eco-friendly deep eutectic solvents - Yuxi Chen; Gonghua Hong; Lei Li; Qing Qu; Guang Li; Jiajie Wu; Lin Ge (Chemical Engineering Journal, 2024)

Positive effects of leguminous shrub encroachment on multiple ecosystem functions of alpine meadows and steppes greatly depended on increasing soil nutrient - Wen Yang; Guangpeng Qu; Austin R. Kelly; Gao-Lin Wu; Jingxue Zhao (CATENA, 2024)

Investigation of topographic amplification on ground motions considering spatial variability of soil properties - Hongjie Fang; Yingxiong Wu; Chuanxiang Qu; Youhan Lin (Stochastic Environmental Research and Risk Assessment, 2024)

Selective uneven enrichment of soil organic carbon among different-sized sediments under a rain-induced overland flow: 13C stable isotope evidence - Lin Liu; Jiuqi Qu; Qianping Hu; Jinling Xu; Enfeng Liu; Zijun Li (Chemosphere, 2024)

Natural and anthropogenic controls on environmental change during the Holocene based on a multi-proxy record obtained from subalpine peatland in southern China - Xiaoxu Qu; Chao Huang; Zhiguo Rao; Liyuan Wu; Yongyi Luo; Fajin Chen; YunXia Li; Lin Zhao; Lidan Liu; Zhiguang Song; Wenfeng Deng (Science of The Total Environment, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Polystyrene nanoplastics affected the nutritional quality of Chlamys farreri through disturbing the function of gills and physiological metabolism: Comparison with microplastics - Yejiao Sun; Xinguo Zhao; Qi Sui; Xuemei Sun; Lin Zhu; Andy M. Booth; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Holocene provenance variations and palaeofloods response to ENSO-driven monsoon precipitation in the subalpine peatland in southern China - Xiaoxu Qu; Chao Huang; Zhiguo Rao; Gangjian Wei; Liyuan Wu; Yongyi Luo; Yunxia Li; Lin Zhao; Lidan Liu; Wenfeng Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Rational construction Ag/LiF/sulfide rich protective layer for remarkably enhancing the stability of Li metal anodes - Caili Xu; Shu Zhang; Cheng Chen; Yunhui Lin; Bing Qu; Haiping Zhou; Mengqiang Wu (Chemical Engineering Journal, 2024)

Mechanism of sulfur-guided CO2 selective hydrogenation through modulation of surface intermediate over Ni/ZrO2 catalysts - Yunhao Zang; Ziyi Zhang; Yan Wang; Jiangying Qu; Feng Gao; Jianfeng Gu; Xuetan Lin; Taipeng Wei (Chemical Engineering Journal, 2024)

The outbreak of Drupella snails and its catastrophic effects on coral reefs: a comprehensive review - Fang Zhang; Xiwang Jia; Zhenni Lin; Yiyi Jiang; Mengjie Qu (Frontiers in Marine Science, 2024)
The recurring outbreaks of Drupella snails are a significant threat to coral reef ecosystems on a global scale. However, research on Drupella snails is currently very fragmentary. This article explores the ecological impacts and mitigation methods of Drupella snails and its outbreaks, and draws the following main conclusions. 1) Drupella snails inhabit the tropical oceans of the Indo-Pacific, utilizing their specialized radula to feed on coral polyps, and they predominantly spawn during summer, attaching egg capsules onto coral skeletons. 2) An outbreak of Drupella snails is defined by a density of > 2 ind/m 2 , but large aggregations alone do not necessarily indicate an outbreak. 3) The damage of coral reef ecosystem is the primary cause of Drupella snail outbreaks, with the hypotheses of “terrestrial nutrient input” and “overfishing of predator” being widely accepted but not fully explaining all outbreak events. 4) Countering Drupella snail outbreaks involves improving the health of coral reef ecosystems, protected areas, biological control and manual removal, though manual removal is the most direct and effective in short-term. 5) The understanding of the physiological and ecological characteristics of Drupella snails is inadequate at present, with larval development and population ecology being areas of particular under-investigation. 6) Studies of Drupella snail outbreaks have focused mainly on mid-outbreak stages, with little attention to early warnings beforehand or adverse outcomes afterwards. Despite significant challenges, addressing knowledge gaps in the biology of Drupella snails is crucial to determine the true causes of their outbreaks and identify corresponding solutions.

Identifying ARG-carrying bacteriophages in a lake replenished by reclaimed water using deep learning techniques - Donglin Wang; Jiayu Shang; Hui Lin; Jinsong Liang; Chenchen Wang; Yanni Sun; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Tigecycline-resistance mechanisms and biological characteristics of drug-resistant Salmonella Typhimurium strains in vitro - Lin Li; Longbo Wang; Shuo Yang; Yanfang Zhang; Yiming Gao; Qianyu Ji; Linran Fu; Qiling Wei; Feifei Sun; Shaoqi Qu (Veterinary Microbiology, 2024)

Redefining virtual water allocation in China based on economic welfare gains from environmental externalities - Yiyi Cao; Yunlei She; Qianzi Wang; Jin Lin; Weiming Chen; Shen Qu; Zhouyi Liu (Journal of Cleaner Production, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

Reducing charge-recombination losses in photovoltaic cells by spontaneous reconstruction of n/p homojunction in a monolithic perovskite film using black phosphorus nanosheets - Lin Fan; Miao Yu; Wanting Hu; Lixue Wang; Zirui Mao; Fengyou Wang; Xiaoyan Liu; Xin Qu; Qiong Wu; Zhaoliang Yu; Lili Yang; Huilian Liu (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Environmental forcing of phytoplankton carbon-to-diversity ratio and carbon-to-chlorophyll ratio: A case study in Jiaozhou Bay, the Yellow Sea - Yingzhe Wang; Zhengguo Cui; Dongsheng Ding; Qian Yang; Lin Zhu; Keming Qu; Jun Sun; Yuqiu Wei (Marine Pollution Bulletin, 2023)

Mineral scaling induced membrane wetting in membrane distillation for water treatment: Fundamental mechanism and mitigation strategies - Haiqing Chang; Yingyuan Zhu; Lin Huang; Zhongsen Yan; Fangshu Qu; Heng Liang (Water Research, 2023)

New insights into the impact of polystyrene micro/nanoplastics on the nutritional quality of marine jacopever (Sebastes schlegelii) - Xuemei Sun; Xuru Wang; Andy M. Booth; Lin Zhu; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Degradation of bisphenol A by Fe-doped BiOBr enhanced UV/persulfate system: Significant role of superoxide radicals - Zezheng Lin; Yang Guo; Xiaoxuan Qu; Yuying Xiang; Shuwen Shen; Xin Zhu (Process Safety and Environmental Protection, 2023)

Long-lived Cenozoic positive relief of the south-Eastern Tian Shan: Insights from provenance analyses of the northwestern Kuqa Depression sediments - Jialun Huang; Xiubin Lin; Kaixuan An; Hanlin Chen; Xiaogan Cheng; Yang Qu; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Zhuxin Chen; Lin Jiang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Oxidative abatement of saccharin by ozone and its influence on DBPs formation during postchlorination - Zezheng Lin; Yang Guo; Xiaoxuan Qu; Yuying Xiang; Xin Zhu (Journal of Water Process Engineering, 2023)

Composition engineering of carbon nanotubes supported Pt RhRu ultrafine nanocatalysts for ethanol electro-oxidation: Elucidating the role of trimetallic sites - Chang Liu; Xinwei Wen; Lin Ge; Yuxi Chen; Jiajie Wu; Qing Qu; Lei Li (Chemical Engineering Journal, 2023)

A Comparative Analysis of Three Rutaceae Species Reveals the Multilayered Mechanisms of Citrus in Response to Huanglongbing Disease - Yunuo Liu; Liting Dong; Danlu Ran; Shuai Wang; Rongrong Qu; Lin Zheng; Aihong Peng; Yongrui He; Shanchun Chen; Xiuping Zou (Journal of Plant Growth Regulation, 2023)

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Characteristics and Geological Significance of High-precision Aeromagnetic Data in LinFen-YunCheng - Ming Wang; Jin-hong Qu; Xiao-xing Lin; Zhen-jun Liu; Fang Li (Applied Geophysics, 2023)

Development and Evaluation of Real-Time Polymerase Chain Reaction (PCR) to Authenticate Sablefish ( Anoplopoma fimbria ) in Commercial Seafood Products - Meng Qu; Yanhua Jiang; Yingying Guo; Wenjia Zhu; Shufang Liu; Na Li; Fengling Li; Lin Yao; Zhijun Tan; Lianzhu Wang (Journal of Aquatic Food Product Technology, 2023)

The complex role of air pollution on the association between greenness and respiratory mortality: Insight from a large cohort, 2009–2020 - Wenjing Wu; Zhicheng Du; Ying Wang; Yuqin Zhang; Shirui Chen; Xu Ju; Gonghua Wu; Zhiqaing Li; Jie Sun; Jie Jiang; Weihua Hu; Ziqiang Lin; et al. (Science of The Total Environment, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

BMSC-exosomes miR-25-3p Regulates the p53 Signaling Pathway Through PTEN to Inhibit Cell Apoptosis and Ameliorate Liver Ischemia‒reperfusion Injury - Hongnan Li; Weidong Lin; Guangzhi Zhang; Runsheng Liu; Minghai Qu; Jiayang Zhang; Xuekun Xing (Stem Cell Reviews and Reports, 2023)

Solar-driven strongly coupled plasmonic Au nanoarrays on mesoporous silica nanodisks enable selective fungal and bacterial inactivation in well water - Zhuoyun Tang; Dingren Ma; Jingling Yang; Jinjuan Chen; Zhuohang Lin; Qiwen Liang; Yimu Jiao; Wei Qu; Dehua Xia (Water Research, 2023)

In-situ investigation into the dynamic evolution of electrode surface H* and H* mediated pH-independent and residue-free electro-Fenton process - Jun Zhang; Songying Qu; Bing Li; Xiaoyan Li; Lin Lin (Chemical Engineering Journal, 2023)

The drought-induced succession decreased ecosystem multifunctionality of alpine swamp meadow - Wen Yang; Jingxue Zhao; Guangpeng Qu; Ruicheng Li; Gao-Lin Wu (CATENA, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

Computer vision-assisted smartphone microscope imaging digital immunosensor based on click chemistry-mediated microsphere counting technology for the detection of aflatoxin B1 in peanuts - Meijie Ren; Yongzhen Dong; Jianlong Wang; Jianhan Lin; Lijie Qu; Yang Zhou; Yiping Chen (Analytica Chimica Acta, 2023)

The control of border pollution: The lure from political promotion incentives - Lin Guo; Jingjing Yang; Xiaodong Qu (Journal of Cleaner Production, 2023)

Nitrogen-coordinated cobalt embedded in hollow carbon polyhedron for catalytic ozonation of odor CH3SH at ambient temperature - Hailin Wen; Wei Qu; Muke Lin; Lingzhi Zhou; Xuexia Guo; Ping Ma; Taoli Wu; Huinan Zhao; Tao Zhong; Chun He (Chemical Engineering Journal, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Boosting the tumor photothermal therapy with hollow CoSnSx-based injectable hydrogel via the sonodynamic and dual-gas therapy - Lu Jia; Yuzhu Wang; Tingting Hu; Chunyu Yang; Huiming Lin; Feng Zhang; Fengyu Qu; Liru Cui; Wei Guo (Chemical Engineering Journal, 2023)

Untangling microbiota diversity and assembly patterns in the world’s longest underground culvert water diversion canal - Mengyao Wang; Xinyong Liu; Liang Qu; Tongtong Wang; Lin Zhu; Jianfeng Feng (Environmental Monitoring and Assessment, 2023)

Parerythrobacter lacustris sp. nov., a novel member of the family Erythrobacteraceae isolated from an inland alpine lake - Maripat Xamxidin; Han Dong; Jia-Yan Wang; Wu Qu; Lin Xu; Min Wu (Archives of Microbiology, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Ocean acidification enhances the embryotoxicity of CuO nanoparticles to Oryzias melastigma - Hao Wang; Qi Sui; Jian Zhao; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2023)

Nitrogen coordination modulation of single-atom CoN4 enables dual-active-sites catalyst featuring synergistic organics adsorption and peroxymonosulfate activation - Jun Zhang; Songying Qu; Bing Li; Xiaoyan Li; Lin Lin (Chemical Engineering Journal, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Degradation mechanisms of 2-chlorophenol by Acinetobacter sp.: Exploring cellular membrane structure, intra- and extracellular components, and transcriptomic analysis - Han Lin; Wenqi Guan; Yibo Xiao; Yujiao Qu; Yuan Ren (Journal of Environmental Chemical Engineering, 2023)

Bio-based tannic acid as a raw material for membrane surface modification - Shiyu Zhou; Yang Qu; Bowen Yang; Qiang Zhang; Jin Wang; Yamei Lin; Zhong Chen; Guo-Ping Lu (Desalination, 2023)

The genetic basis of the leafy seadragon’s unique camouflage morphology and avenues for its efficient conservation derived from habitat modeling - Meng Qu; Yingyi Zhang; Zexia Gao; Zhixin Zhang; Yali Liu; Shiming Wan; Xin Wang; Haiyan Yu; Huixian Zhang; Yuhong Liu; Ralf Schneider; Axel Meyer; et al. (Science China Life Sciences, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Developing a novel framework to re-examine half a century of compound drought and heatwave events in mainland China - Lin Zhao; Xinxin Li; Zhijiang Zhang; Moxi Yuan; Shao Sun; Sai Qu; Mengjie Hou; Dan Lu; Yajuan Zhou; Aiwen Lin (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Real-time outlier detection in integrated GNSS and accelerometer structural health monitoring systems based on a robust multi-rate Kalman filter - Xuanyu Qu; Xiaoli Ding; You-Lin Xu; Wenkun Yu (Journal of Geodesy, 2023)

Charge-dependent negative effects of polystyrene nanoplastics on Oryzias melastigma under ocean acidification conditions - Yufei Chen; Xia Wang; Qi Sui; Guozhu Chang; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

Rapid expansion of wetlands on the Central Tibetan Plateau by global warming and El Niño - Yang Li; Zhengyang Hou; Liqiang Zhang; Changqing Song; Shilong Piao; Jintai Lin; Shushi Peng; Keyan Fang; Jing Yang; Ying Qu; Yuebin Wang; Jingwen Li; et al. (Science Bulletin, 2023)

Metagenomic study of carbon metabolism in black soil microbial communities under lead-lanthanum stress - Yue Tao; Lu Shen; Siyue Han; Zixu Li; Yunhe Cui; Yulong Lin; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2023)

Expired yogurt-derived, three-dimensional water evaporator with sustainable self-cleaning and high mechanical properties for the desalination and purification of oil-contaminated seawater - Yahui Liu; Yitong Cui; Chunyu Yang; Huiming Lin; Feng Zhang; Kai Yu; Wei Guo; Fengyu Qu (Desalination, 2023)

Simultaneous dual-defect engineering as a booster for polysulfide adsorption and conversion in Li-S battery - Meixiu Qu; Yu Bai; Weiwei Yang; Lin Peng; Zhenhua Wang; Wang Sun; Kening Sun (Chemical Engineering Journal, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

The Novel Fluorescent Probe Toward Yttrium(III) and its Bioimaging - Yuxin Qin; Qian Meng; Junxiong Yao; Mengyu Chen; Yajie Dong; Dashuo Chen; Shuping He; Cuibing Bai; Lin Zhang; Biao Wei; Hui Miao; Changqing Qu; et al. (Journal of Fluorescence, 2023)

Dam construction alters planktonic microbial predator‒prey communities in the urban reaches of the Yangtze River - Qiaojuan Wang; Junwen Chen; Weixiao Qi; Donglin Wang; Hui Lin; Xinghua Wu; Dianchang Wang; Yaohui Bai; Jiuhui Qu (Water Research, 2023)

Dosing with pyrite significantly increases anammox performance: Its role in the electron transfer enhancement and the functions of the Fe-N-S cycle - Fan Feng; Zhigong Liu; Xi Tang; Xing Wu; Caiyan Qu; Seow Wah How; Di Wu; Ruiyang Xiao; Chong-Jian Tang; Zhang Lin; Liyuan Chai; Guang-Hao Chen (Water Research, 2023)

Cohesive zone model based reliability analysis for a sandwich pipe - Yangyang Qu; Nian-Zhong Chen; Lin Yuan (Ocean Engineering, 2023)

Arsenic effects and behavior during the transformation of struvite to newberyite: Implications for applications of green fertilizers - Jinru Lin; Yidi Wang; Yuanming Pan; Shaofeng Wang; Xiaoming Zhao; Shan Qu; Zhenbing She; Kenan Cao; Zidan Yuan; Xu Ma; Reza Deevsalar; Yongfeng Jia (Chemical Engineering Journal, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Numerical analysis of engineered metabarrier effect on ground vibration induced by underground high-speed train - Shuai Qu; Lin Zhao; Jizhong Yang; Zaixin Wu; Shengyang Zhu; Wanming Zhai (Soil Dynamics and Earthquake Engineering, 2023)

The contribution of fish and seaweed mariculture to the coastal fluxes of biogenic elements in two important aquaculture areas, China - Yonglong Xiong; Lin Gao; Liyin Qu; Juntian Xu; Zengling Ma; Guang Gao (Science of The Total Environment, 2023)

Hollow Co-CeO2@PEG nanospheres: Ultrasound enhanced cascade-nanozyme for synergetic anticancer - Miao Wang; Stephen Choi; Qingchen Bai; Kai Yu; Wei Guo; Feng Zhang; Ran Jia; Fengyu Qu; Huiming Lin (Chemical Engineering Journal, 2023)

Surface adsorption guided design of semicrystalline nickel-iron hydroxide for highly-sensitive glucose sensing - Minyuan Tan; Ming Ni; Xinyu Liu; Bo Qu; Xi Lin; Daochuan Jiang; Yupeng Yuan; Haiwei Du (Chemical Engineering Journal, 2023)

Phycospheric bacterial community structure and function succession during the typical harmful macroalgal blooms - Tongfei Qu; Chengzong Hou; Chen Guan; Xinyu Zhao; Jun Chen; Yi Zhong; Jinhui Xu; Zhihao Lin; Yu Xu; Xuexi Tang; Ying Wang (Frontiers in Marine Science, 2022)
Based on the diversity and importance of phycospheric microorganisms as well as their complex interaction with algae, their ecological correlation with algal bloom events has become a research topic of great interest that remains unclear in the natural dynamic process of harmful macroalgal blooms (HMBs). The world’s largest green tides caused by macroalgae Ulva prolifera have occurred in the Yellow Sea for 16 consecutive years, and seriously affected the coastal ecosystem. Here, we monitored the spatiotemporal dynamics of the phycospheric bacterial community during the U . prolifera green tide bloom. The 73-day continuous field survey covered the whole process of initial invasion until the extinction of the green tide. The phycospheric bacterial community has a higher richness than the control seawater bacteria; in addition, it has more enriched taxa with organic nutrition preference and environmental pressure adaption, such as Bacteroidetes, Firmicutes, and Desulfobacterota. The same differences in populations and functional profiles were observed among the epiphytic bacterial and phycospheric seawater bacterial communities, which may be driven by the spatial heterogeneity of biogenic elements (e.g., organic nutrients and oxygen) among the habitats. Significant succession occurred in both the epiphytic bacterial and phycospheric seawater bacterial communities; their diversity and richness exhibited significant heterogeneity variation patterns, and their community structure became more similar in late phases. Our study revealed that macroalgal phycospheric microbial communities have a highly complex and dynamic composition and variable ecological functions, which indicate that phycospheric microorganisms are closely related to the fate of HMBs and may have the profound effect coastal biogeochemical cycles.

Effect of Schizochytrium limacinum supplementation to a low fish-meal diet on growth performance, lipid metabolism, apoptosis, autophagy and intestinal histology of Litopenaeus vannamei - Xinzhou Yao; Yingying Lin; Menglin Shi; Liutong Chen; Kangyuan Qu; Yucheng Liu; Beiping Tan; Shiwei Xie (Frontiers in Marine Science, 2022)
In this experiment, we aimed to evaluate the relationship between the addition of Schizochytrium limacinum to low fish meal diets on growth performance, apoptosis, autophagy, lipid metabolism, and intestinal health of Lipenaeus vanamei . The diet containing 25% fish meal was used as a positive control (FM) and the other three diets contained 15% fish meal and were supplemented with 0, 0.3, and 0.6% S. Limacinum (LF, LFLD, LFHD). The shrimp (0.22 ± 0.00 g) were divided into four replicates of 40 shrimp per tank and fed four times daily to apparent satiation for 8 weeks. Results showed that the final weight (FBW) and weight gain rate (WGR) of shrimp fed FM and LFHD diets were significantly increased compared to those fed the LFLD diet ( P <0.05), and there was no significant difference in survival rate (SR) and feed conversion rate (FCR) among the groups ( P >0.05). Supplementation of S. Limacinum in low fish meal diets had no effects on shrimp body composition ( P <0.05). There were significant differences ( P <0.05) in low-density lipoprotein (LDL-C) glucose (GLU), triglycerides (TG), and total cholesterol (TC) in the hemolymph of shrimp fed the LF diet compared to those fed the LFLD and LFHD diets. HE staining and transmission electron microscopy (TEM) results showed that the microvilli height, mucosal folds height, mucosal folds width and muscle layer thickness in the intestine of shrimp fed the LF diet were significantly reduced compared to those fed the other three diets ( P <0.05). Swelling of the endoplasmic reticulum and irregular mitochondria in the gut of shrimp fed the LF diet was also observed by TEM, and the endoplasmic reticulum and mitochondria of shrimp fed the LFHD diet returned to a healthy state. Hepatopancreas genes expression results were showed that the gene expression of 5′ -AMP-activated protein kinase ( ampk ), stearoyl-CoA desaturase ( scd1 ), acetyl-CoA carboxylase 1 ( acc1 ), and malonyl-CoA decarboxylase ( mcd ) of shrimp fed the LF diet was significantly increased compared to those fed the FM diet ( P <0.05). The gene expression of sterol regulatory element-binding protein ( srbep ) and carnitine palmitoyl transferase 1 ( cpt-1 ) of shrimp fed the LFLD diet was significantly increased compared to those fed the LF diet ( P <0.05). The gene expression of acc1, mcd and scd1 of shrimp fed the LFHD diet was significantly reduced compared to those fed the LF diet ( P <0.05). Results of genes expression associated with apoptosis in the hepatopancreas showed that the gene expression of B lymphocytoma-2 ( bcl-2 ), BCL2 associated X apoptosis regulator ( bax ) and cysteinyl aspartate specific proteinase 8 ( caspase 8 ) of shrimp fed the LF diet was significantly reduced compared to those fed the FM diet ( P <0.05). The gene expression of bcl-2 of shrimp fed the LFHD diet was significantly reduced compared to those fed the LF diet ( P <0.05). Genes related to autophagy in the hepatopancreas showed that the expression of autophagy-related protein 12 ( atg 12 ), autophagy-related protein 13 ( atg 13 ) and beclin1 of shrimp fed LF the diet was significantly reduced compared to those fed the FM diet ( P <0.05). The gene expression of atg 12 and atg 13 of shrimp fed the LFHD diet was significantly increased compared to those fed the LF diet ( P <0.05). In summary, reducing fish meal is detrimental to the growth performance and intestinal health of shrimp, and 0.6% S. Limacinum supplementation can improve the growth performance, promotes hepatopancreas lipid metabolism, reduces apoptosis, promotes autophagy and improve intestinal health of Litopenaeus vannamei .

Taxonomy and phylogeny of Pseudovorticella ciliates (Ciliophora, Peritrichia): Two new and one rare species from the coastal waters of China - Yong Zhang; Ying Yu; Zhishuai Qu; Mengmeng Jiang; Zhuo Shen; Jiqiu Li; Xiaofeng Lin (Frontiers in Marine Science, 2022)
Peritrich ciliates are a species-rich group of sessile unicellular eukaryotes, which can be found in various aquatic habitats from all over the world. It is well accepted that there are still many ciliates to be uncovered. During a survey on ciliate biodiversity in the coastal waters of China, three solitary peritrich species were identified as members of the genus Pseudovorticella Foissner & Schiffmann, 1975, including two new species and a rare one. Pseudovorticella zhejiangensis sp. n. differs from its congeners mainly by having a conical-shaped zooid, conspicuous pellicular blisters, one ventral and one dorsal contractile vacuoles, and an infundibular polykinety 3 with three rows of nearly equal length but different beginning positions. Pseudovorticella dalianensis sp. n. can be defined mainly by an obovoid-shaped zooid, one ventral contractile vacuole, and a three-rowed infundibular polykinety 3 with the middle row being the longest. The rare species, Pseudovorticella verrucosa (Dons, 1915) Sun et al., 2009, was redescribed. The small subunit (SSU) rDNA sequences of these three species were sequenced for the first time, the phylogeny of Pseudovorticella species was analyzed, and the results verified the non-monophyly of this genus. This study demonstrates that the morphologic and gene barcoding data are the optimum combination to disclose the biodiversity of ciliates.

Iron metabolism, ferroptosis, and lncRNA in cancer: knowns and unknowns - Lei Qu; Xinyu He; Qian Tang; Xiao Fan; Jian Liu; Aifu Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Identifying Patients with Epilepsy Having Depression/Anxiety Disorder Using Common Spatial Patterns of Functional EEG Networks - Yuanyuan Zhang; Yuhang Lin; Zhichuang Qu; Zhi Zhang; Daqing Guo; Xin Chen; Haifen Shu; Sixun Yu (Journal of Medical and Biological Engineering, 2022)

Progress of Selenium Deficiency in the Pathogenesis of Arthropathies and Selenium Supplement for Their Treatment - Huan Deng; Haobiao Liu; Zhihao Yang; Miaoye Bao; Xue Lin; Jing Han; Chengjuan Qu (Biological Trace Element Research, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

The different effects of intramuscularly-injected lactate on white and brown adipose tissue in vivo - Yaqian Qu; Siyu Chen; Lei Zhou; Min Chen; Lin Li; Yihan Ni; Jingquan Sun (Molecular Biology Reports, 2022)

Ecological risk assessment of metallic nanoparticles on the marine environments: Species sensitivity distributions analysis - Sulan Feng; Lin Zhu; Xinguo Zhao; Qi Sui; Xuemei Sun; Bijuan Chen; Keming Qu; Bin Xia (Frontiers in Marine Science, 2022)
Metallic nanoparticles (NPs) are increasingly being used and inevitably entering the marine environment. Therefore, the adverse effects of NPs on individual marine species have attracted increasing attentions. However, to date, the ecological risks of NPs on the marine ecosystem remain poorly understood. In this study, species sensitivity distributions (SSDs) were constructed for Ag, ZnO, CuO, and TiO 2 NPs to understand their ecotoxicity to the marine ecosystem and the contribution of size effect and ion effect to the nanotoxicity. Furthermore, a case study on the assessment of marine ecological risk and marine environment carrying capacity of metallic NPs was performed in Jiaozhou Bay, China. The results showed the toxicity of metallic NPs to marine species following the order of Ag > ZnO > CuO > TiO 2 . Both size effect and ion effect contributed to the toxicity of NPs. Environmental concentrations of Ag, ZnO, CuO, and TiO 2 NPs are much lower than the predicted no-effect concentrations, indicating that these metallic NPs have not yet posed risks to the marine ecosystem based on currently limited measured environmental concentrations of metallic NPs in seawater. And the marine environment carrying capacity of Ag, ZnO, CuO, and TiO 2 NPs in Jiaozhou Bay seawater were determined to be 5.03, 8.72, 93.06, and 629.79 t, respectively. The results help us understand the ecological risk of NPs in marine environments and provide a scientific basis for the sustainable development of nanotechnology.

CREB1 contributes colorectal cancer cell plasticity by regulating lncRNA CCAT1 and NF-κB pathways - Bin Li; Lisi Zheng; Jiayi Ye; Chenmin Zhang; Jie Zhou; Qiaojuan Huang; Yanhua Guo; Luqin Wang; Peng Yu; Shurong Liu; Qiao Lin; Yuxia Luo; et al. (Science China Life Sciences, 2022)

The IRE1/JNK signaling pathway regulates inflammation cytokines and production of glomerular extracellular matrix in the acute kidney injury to chronic kidney disease transition - Yan Liang; Lingyun Qu; Zhenjie Liu; Lulu Liang; Yingzi Wang; Songxia Quan; Yulin Wang; Lin Tang (Molecular Biology Reports, 2022)

LncRNA BACE1-AS promotes the progression of osteosarcoma through miR-762/SOX7 axis - Chunlei Wang; Tao Zhang; Lin Yang; Xinyu Na; Yanlong Qu (Molecular Biology Reports, 2022)

Characterization of Water Transport in Porous Building Materials Based on an Analytical Spontaneous Imbibition Model - Ming-Liang Qu; Sheng-Yue Lu; Qingyang Lin; Sajjad Foroughi; Zi-Tao Yu; Martin J. Blunt (Transport in Porous Media, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

Long non-coding RNAs regulate fatty acid and cholesterol metabolism - Kai Lei; Lei Qu; Fangzhou Liu; Ninghui Hao; Jincheng Chen; Jian Liu; Aifu Lin (Genome Instability & Disease, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Wnt8a is one of the candidate genes that play essential roles in the elongation of the seahorse prehensile tail - Bo Zhang; Geng Qin; Lili Qu; Yanhong Zhang; Chunyan Li; Chunlei Cang; Qiang Lin (Marine Life Science & Technology, 2021)

Functional analysis of indole 3-hexanoic acid as a novel auxin from Arabidopsis thaliana - Ping Song; Hui Xu; Jixiu Zhang; Huatao Chen; Li Li; Yana Qu; Feng Lin; Qun Zhang (Planta, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

Effects of Heat Stress on Gut Microbiome in Rats - Qian Qu; Hua Li; Lin Bai; Shiwei Zhang; Jiaqi Sun; Weijie Lv; Chunxin Ye; Cui Liu; Dayou Shi (Indian Journal of Microbiology, 2021)
Gut microbiome, as the largest and most important micro-ecosystem, plays a critical role in health. The purpose of this study was to evaluate whether heat stress modulates the composition and diversity of the gut microbiome in rats. The heat stress model was prepared in rats with the heating temperature maintained at 35–38°C. Cecum contents were collected after heat stress for 3 h and days 1, 3 and 7. Total DNA was extracted for 16 S rRNA sequencing and analysis of intestinal microbiome composition and diversity. The study showed that the composition of the intestinal microbiome of heat stress group was changed. And the heat stress modulated key phylotypes of gut microbiota at the level of phylum and genus. In particular, the genus of Lactobacillus and Bacteroides were significantly reduced, whereas the Oscillospira and Clostridium were increased by heat stress. Meanwhile, the rats under the heat stress encountered the change in carbohydrate metabolism, amino acid metabolism, and membrane transport to defense against stress. Taken together, the composition and structure of gut microbiome were affected by heat stress and some key phylotypes were also significantly altered. We conclude that the heat stress could impact multiple biological functions, via altering the gut microbiome.

An eco‐city design methodology for hilly areas of western China - Kai Lin; Zhengwei He; Zhujun Zhao; Jiaxin Chang; Keran Tang; Rui Qu; Li He (Earth Science Informatics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Impact factors of the accumulation, migration and spread of antibiotic resistance in the environment - Zibo Lin; Tao Yuan; Lai Zhou; Sen Cheng; Xu Qu; Ping Lu; Qiyan Feng (Environmental Geochemistry and Health, 2021)

The relationship between ambient temperature and acute respiratory and cardiovascular diseases in Shenyang, China - Yang Shen; Xudong Zhang; Cai Chen; Qianqian Lin; Xiyuan Li; Wenxiu Qu; Xuejian Liu; Li Zhao; Shijie Chang (Environmental Science and Pollution Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Correction to: Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2020)

Correction to: CircUBAP2 promotes SEMA6D expression to enhance the cisplatin resistance in osteosarcoma through sponging miR-506-3p by activating Wnt/β-catenin signaling pathway - Xuelian Gong; Wei Li; Lin Dong; Fangfei Qu (Journal of Molecular Histology, 2020)
The authors of the article want to add Xuelian Gong and Wei Li as the first author and co-first author as they have greatly contributed to the revision work. The correct author group is given in this Correction.

CircUBAP2 promotes SEMA6D expression to enhance the cisplatin resistance in osteosarcoma through sponging miR-506-3p by activating Wnt/β-catenin signaling pathway - Lin Dong; Fangfei Qu (Journal of Molecular Histology, 2020)
The occurrence of chemo-resistance is an essential reason for the high morbidity of osteosarcoma (OS) patients. Circular RNAs (circRNAs) have been involved in the regulation of chemo-resistance in cancers. Semaphorins 6D (SEMA6D) is abnormally expressed in many cancers. However, the roles of circUBAP2 and SEMA6D in the chemo-resistance of OS are still unclear. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression levels of circUBAP2, SEMA6D and microRNA-506-3p (miR-506-3p). The cisplatin resistance and proliferation of cells were evaluated by 3-(4, 5-dimethyl-2 thiazolyl)-2, 5-diphenyl-2- H -tetrazolium bromide assay. Western blot analysis was performed to measure the protein levels of Wnt/β-catenin signaling pathway biomarkers and SEMA6D. Also, the apoptosis, migration and invasion of cells were assessed by Flow cytometry and Transwell assays, respectively. Besides, Dual-luciferase reporter assay was used to verify the interaction between miR-506-3p and circUBAP2 or SEMA6D. We found that the expression levels of circUBAP2 and SEMA6D were increased in cisplatin-resistant OS tissues and cells. Knockdown of circUBAP2 inhibited the cisplatin resistance, silenced Wnt/β-catenin signaling pathway, hindered cell proliferation, migration and invasion, and promoted apoptosis in cisplatin-resistant OS cells, all of which could be reversed by overexpression of SEMA6D. MiR-506-3p could be sponged by circUBAP2 and could target SEMA6D. The suppression of miR-506-3p overexpression on the progression of OS cisplatin resistance could be reversed by SEMA6D overexpression, while miR-506-3p inhibitor also could invert the inhibitory effect of circUBAP2 silencing on the progression of OS cisplatin resistance. In conclusion, CircUBAP2 and SEMA6D played active roles in the progression of OS cisplatin resistance through miR-506-3p, which might provide some new ideas for studying the countermeasures of OS resistance.

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Ribosome profiling analysis identified a KRAS-interacting microprotein that represses oncogenic signaling in hepatocellular carcinoma cells - Wenli Xu; Bing Deng; Penghui Lin; Chang Liu; Bin Li; Qiaojuan Huang; Hui Zhou; Jianhua Yang; Lianghu Qu (Science China Life Sciences, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Development and Evaluation of a Novel Armored RNA Technology Using Bacteriophage Qβ - Lin Yao; Fengling Li; Meng Qu; Yingying Guo; Yanhua Jiang; Lianzhu Wang; Yuxiu Zhai (Food and Environmental Virology, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Rapamycin Removes Damaged Mitochondria and Protects Human Trabecular Meshwork (TM-1) Cells from Chronic Oxidative Stress - Jing Na He; Shao Dan Zhang; Yang Qu; Hai Lin Wang; Clement C. Tham; Chi Pui Pang; Wai Kit Chu (Molecular Neurobiology, 2019)

Selective feeding of bay scallop Argopecten irradians on phytoplankton community revealed by HPLC analysis of phytopigments in Bohai Sea, China - Tao Jiang; Longhua Wang; Fuchong Zhang; Xiao Fang; Lin Lu; Jihong Zhang; Wei Wang; Keming Qu; Chao Chai (Journal of Oceanology and Limnology, 2019)

Projections of East Asian summer monsoon under 1.5 °C and 2 °C warming goals - Lin Chen; Xia Qu; Gang Huang; Yuanfa Gong (Theoretical and Applied Climatology, 2019)

Variations in land surface phenology and their response to climate change in Yangtze River basin during 1982–2015 - Moxi Yuan; Lunche Wang; Aiwen Lin; Zhengjia Liu; Sai Qu (Theoretical and Applied Climatology, 2019)

Cold water immersion test (10 °C, 10 min) for diagnosing vibration-induced white finger among a group of polishers in a subtropical environment - Bin Xiao; Danying Zhang; Maosheng Yan; Hongying Qu; Wei Wen; Xiao Zhang; Hansheng Lin; Ying Ye; Ting Chen; Qingsong Chen (International Archives of Occupational and Environmental Health, 2019)

Comparison of monoculture and mixed culture (Scenedesmus obliquus and wild algae) for C, N, and P removal and lipid production - Zhi Qu; Pengfei Duan; Xubing Cao; Manli Liu; Li Lin; Ming Li (Environmental Science and Pollution Research, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

The complete genome of the antifungal bacterium Pseudomonas sp. strain MS82 - Lin Ma; Shaoxuan Qu; Jinsheng Lin; Jiayuan Jia; Sonya M. Baird; Ning Jiang; Huiping Li; Lijuan Hou; Shi-En Lu (Journal of Plant Diseases and Protection, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Ginsenoside Compound K Regulates Amyloid β via the Nrf2/Keap1 Signaling Pathway in Mice with Scopolamine Hydrobromide-Induced Memory Impairments - Qing Yang; Jianan Lin; Huiyuan Zhang; Yingna Liu; Mo Kan; Zhiru Xiu; Xijun Chen; Xingcheng Lan; Xiaohua Li; Xiaozheng Shi; Na Li; Xiaobo Qu (Journal of Molecular Neuroscience, 2019)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Succession of phytoplankton functional groups from spring to early summer in the central Bohai Sea using HPLC–CHEMTAX approaches - Lin Lu; Tao Jiang; Yong Xu; Yaoyang Zheng; Bijuan Chen; Zhengguo Cui; Keming Qu (Journal of Oceanography, 2018)

Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species - Zhishuai Qu; Lifang Li; Xiaofeng Lin; Thorsten Stoeck; Hongbo Pan; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

Distribution, contamination and accumulation of heavy metals in water, sediments, and freshwater shellfish from Liuyang River, Southern China - Yuyu Jia; Lin Wang; Zhipeng Qu; Zhaoguang Yang (Environmental Science and Pollution Research, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Southern European rainfall reshapes the early-summer circumglobal teleconnection after the late 1970s - Zhongda Lin; Fei Liu; Bin Wang; Riyu Lu; Xia Qu (Climate Dynamics, 2017)

Melatonin Attenuates Early Brain Injury via the Melatonin Receptor/Sirt1/NF-κB Signaling Pathway Following Subarachnoid Hemorrhage in Mice - Lei Zhao; Haixiao Liu; Liang Yue; Jingbo Zhang; Xia Li; Bodong Wang; Yan Lin; Yan Qu (Molecular Neurobiology, 2017)

Effects on heavy metal accumulation in freshwater fishes: species, tissues, and sizes - Yuyu Jia; Lin Wang; Zhipeng Qu; Chaoyi Wang; Zhaoguang Yang (Environmental Science and Pollution Research, 2017)

Effects of sand burial on the survival and growth of two shrubs dominant in different habitats of northern China - Hao Qu; Ha-Lin Zhao; Xue-Yong Zhao; Xiao-An Zuo; Shao-Kun Wang; Min Chen (Environmental Monitoring and Assessment, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

Influenza virus infection induces translocation of apoptosis-inducing factor (AIF) in A549 cells: role of AIF in apoptosis and viral propagation - Xinyan Qu; Xiaoran Ding; Ming Duan; Jing Yang; Ruxian Lin; Zhe Zhou; Shengqi Wang (Archives of Virology, 2017)

Effects of nitrogen and phosphorus on the growth of Levanderina fissa: How it blooms in Pearl River Estuary - Zhaohui Wang; Xin Guo; Linjian Qu; Langcong Lin (Journal of Ocean University of China, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

PRL-3 promotes gastric cancer migration and invasion through a NF-κB-HIF-1α-miR-210 axis - Cheng Zhang; Wei Tian; Lin Meng; Like Qu; Chengchao Shou (Journal of Molecular Medicine, 2016)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Applying systematic conservation planning to constitute a protection strategy for broad-leaved Korean pine forests in Changbai Mountains, China - Lin Ma; Gong-qi Sun; Yi Qu; Jun-qing Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Development of SNP markers in lined seahorse (Hippocampus erectus) based on transcriptome sequencing - Hongyue Qu; Wei Luo; Qiang Lin (Conservation Genetics Resources, 2016)

CarHSFB2, a Class B Heat Shock Transcription Factor, Is Involved in Different Developmental Processes and Various Stress Responses in Chickpea (Cicer Arietinum L.) - Hao Ma; Chuntao Wang; Bin Yang; Huiying Cheng; Ze Wang; Abudoukeyumu Mijiti; Cai Ren; Guanghang Qu; Hua Zhang; Lin Ma (Plant Molecular Biology Reporter, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Characterisation of oligosaccharides from Baizhu by HILIC-MS - Zhe Lin; Yan-Fang Liu; Yang Qu; Li-Ying Shi; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2015)

Analysis of hydrological drought frequency for the Xijiang River Basin in South China using observed streamflow data - Zhiyong Wu; Qingxia Lin; Guihua Lu; Hai He; John J. Qu (Natural Hazards, 2015)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Identification of a novel compound heterozygous mutation in PTPRQ in a DFNB84 family with prelingual sensorineural hearing impairment - Qing Sang; Honglin Mei; Ahan Kuermanhan; Ruizhi Feng; Luo Guo; Ronggui Qu; Yao Xu; Huawei Li; Li Jin; Lin He; Lei Wang (Molecular Genetics and Genomics, 2015)

Improved activity of the Cel5A endoglucanase in Saccharomyces cerevisiae deletion mutants defective in oxidative stress defense mechanisms - Guochao Wu; Jintang Sun; Shanshan Yu; Quanchao Dong; Guoqiang Zhuang; Weifeng Liu; Jianqiang Lin; Yinbo Qu (Biotechnology Letters, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Degradation and dechlorination of pentachlorophenol by microwave-activated persulfate - Chengdu Qi; Xitao Liu; Wei Zhao; Chunye Lin; Jun Ma; Wenxiao Shi; Qu Sun; Hao Xiao (Environmental Science and Pollution Research, 2015)

Blockade of the Activation of T Cells Around β-Cell by the Targeted CTLA-4 Ig at the Surface of β-Cell - Wei Qu; Lin Li; Chendong Han; Meihua Li; Jing Wang; Chaohui Yin; Jing Zhang; Zhaoshun Jiang (Cell Biochemistry and Biophysics, 2015)

Impact of Epoxide Hydrolase 1 Polymorphisms on Lung Cancer Susceptibility in Asian Populations - Wei Yu; Zhi Lin; Baolin Qu (Cell Biochemistry and Biophysics, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Equatorward shift of the South Asian high in response to anthropogenic forcing - Xia Qu; Gang Huang; Kaiming Hu; Shang-Ping Xie; Yan Du; Xiao-Tong Zheng; Lin Liu (Theoretical and Applied Climatology, 2015)

Genetic association study between INSULIN pathway related genes and high myopia in a Han Chinese population - Xiaoqi Liu; Pu Wang; Chao Qu; Hong Zheng; Bo Gong; Shi Ma; He Lin; Jing Cheng; Zhenglin Yang; Fang Lu; Yi Shi (Molecular Biology Reports, 2015)

Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2014)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Zinc finger nuclease: a new approach for excising HIV-1 proviral DNA from infected human T cells - Xiying Qu; Pengfei Wang; Donglin Ding; Xiaohui Wang; Gongmin Zhang; Xin Zhou; Lin Liu; Xiaoli Zhu; Hanxian Zeng; Huanzhang Zhu (Molecular Biology Reports, 2014)

Phosphatidic acid integrates calcium signaling and microtubule dynamics into regulating ABA-induced stomatal closure in Arabidopsis - Yan Jiang; Kai Wu; Feng Lin; Yana Qu; Xiaoxiang Liu; Qun Zhang (Planta, 2014)

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Molecular cloning, expression, purification and characterization of thioredoxin from Antarctic sea-ice bacteria Pseudoalteromonas sp. AN178 - Quanfu Wang; Yanhua Hou; Junjie Qu; Yanyan Hong; Yifei Lin; Xiao Han (Molecular Biology Reports, 2013)

Quantitative and qualitative characteristics of dissolved organic matter from eight dominant aquatic macrophytes in Lake Dianchi, China - Xiaoxia Qu; Li Xie; Ying Lin; Yingchen Bai; Yuanrong Zhu; Fazhi Xie; John P. Giesy; Fengchang Wu (Environmental Science and Pollution Research, 2013)

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

Micromonospora haikouensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Zhi Qu; Hai-peng Lin; Lei Li; Kui Hong (Antonie van Leeuwenhoek, 2012)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Asn64-glycosylation affects Hypocrea jecorina (syn. Trichoderma reesei) cellobiohydrolase Cel7A activity expressed in Pichia pastoris - Guochao Wu; Lianguo Wei; Weifeng Liu; Jianqiang Lin; Lushan Wang; Yinbo Qu; Guoqiang Zhuang (World Journal of Microbiology and Biotechnology, 2010)

A cell strain cloned from Spodoptera exigua cell line (IOZCAS-Spex-II) highly susceptible to S. exigua nucleopolyhedrovirus infection - Huan Zhang; Yong-an Zhang; Qilian Qin; Xuan Li; Lin Miao; Yuzhu Wang; Liangjian Qu; Aijun Zhang; Qing Yang (In Vitro Cellular & Developmental Biology - Animal, 2009)

Z f-and-H sys-based C m measurement under the whole-cell patch-clamp recording - Hao Zhang; Jie Luo; Jun Xiong; Xian-Guang Lin; Zheng-Xing Wu; Anlian Qu (Pflügers Archiv - European Journal of Physiology, 2009)

Nonlinear continuum of egg size-number trade-offs in a snake: is egg-size variation fitness related? - Xiang Ji; Wei-Guo Du; Yan-Fu Qu; Long-Hui Lin (Oecologia, 2009)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Acute toxicity of the pesticide methomyl on the topmouth gudgeon (Pseudorasbora parva): mortality and effects on four biomarkers - Huixian Li; Hui Jiang; Xiwu Gao; Xiaojun Wang; Weigang Qu; Ronghua Lin; Jiao Chen (Fish Physiology and Biochemistry, 2008)

Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Expression and functional analysis of ZmDWF4, an ortholog of Arabidopsis DWF4 from maize (Zea mays L.) - Tingsong Liu; Jinpeng Zhang; Maoyan Wang; Zhangying Wang; Guifen Li; Lin Qu; Guoying Wang (Plant Cell Reports, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mercury pollution in two typical areas in Guizhou province, China and its neurotoxic effects in the brains of rats fed with local polluted rice - Jinping Cheng; Tao Yuan; Wenhua Wang; Jinping Jia; Xueyu Lin; Liya Qu; Zhenhua Ding (Environmental Geochemistry and Health, 2006)

The MYB Transcription Factor Superfamily of Arabidopsis: Expression Analysis and Phylogenetic Comparison with the Rice MYB Family - Chen Yanhui; Yang Xiaoyuan; He Kun; Liu Meihua; Li Jigang; Gao Zhaofeng; Lin Zhiqiang; Zhang Yunfei; Wang Xiaoxiao; Qiu Xiaoming; Shen Yunping; Zhang Li; et al. (Plant Molecular Biology, 2006)

Genetic variability in Gymnodiniaceae ITS regions: implications for species identification and phylogenetic analysis - Peng Shao; Yue-Qin Chen; Hui Zhou; Jie Yuan; Liang-Hu Qu; Di Zhao; Yong-Shui Lin (Marine Biology, 2004)

A deletion mutation in the ?A1/A3 crystallin gene (CRYBA1/A3) is associated with autosomal dominant congenital nuclear cataract in a Chinese family - Yanhua Qi; Hongyan Jia; Shangzhi Huang; Hui Lin; Jingzhi Gu; Hong Su; Tieying Zhang; Ya Gao; Lijun Qu; Dandan Li; Ying Li (Human Genetics, 2004)

Detection and analysis of QTLs for ferrous iron toxicity tolerance in rice, Oryza sativa L. - Jian-lin Wan; Hu-qu Zhai; Jian-min Wan; H. Ikehashi (Euphytica, 2003)

Recovery of transgenic orchid plants with hygromycin selection by particle bombardment to protocorms - Zhihua Yu; Minyong Chen; Lin Nie; Huafei Lu; Xiaotian Ming; Honghong Zheng; Li-Jia Qu; Zhangliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)